Laminated Sheets

By stacking a peeling film with high smoothness on both sides of the adhesive layer, the problem of insufficient optical homogeneity of the adhesive layer in the prior art is solved, and the high smoothness and optical homogeneity of the adhesive layer are achieved. Suitable for applications with high optical requirements.

CN112571879BActive Publication Date: 2025-02-14NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202011065791.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-30
Publication Date
2025-02-14
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

In applications with high optical requirements, it is difficult to achieve optical homogeneity of the adhesive layer, especially in high definition display devices.

Method used

By laminating a high smoothness peeling film on the first and second surfaces of the adhesive layer, optical homogeneity of the adhesive layer is ensured. Specific measures include using a film with a surface with a high smoothness surface in contact with the adhesive layer, and ensuring that the total thickness of the peeling film reaches 80 μm or more.

Benefits of technology

The adhesive layer is highly smooth and optical homogeneous, and is suitable for applications with high optical requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112571879B_ABST
    Figure CN112571879B_ABST
Patent Text Reader

Abstract

The present invention provides a laminated sheet, comprising: an adhesive layer, a first film laminated on a first surface of the adhesive layer, and a second film laminated on a second surface of the adhesive layer. The first film is a release film whose surface in contact with the adhesive layer, i.e., surface A, serves as a release surface. The maximum peak height Rp of the surface A of the first film is 1A The total thickness T of the first thin film and the second thin film of the laminate is less than 50 nm. SUM It is 80μm or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to laminated sheets. Background Art

[0002] Generally speaking, adhesives (also called pressure-sensitive adhesives, the same below) are in a soft solid (viscoelastic) state in a temperature range near room temperature, and have the property of being easily bonded to an adherend by pressure. Utilizing this property, adhesives are typically widely used in various industrial fields from household appliances to automobiles, office equipment, etc. in the form of adhesive sheets containing a layer of the adhesive. As technical documents related to adhesive sheets, Patent Document 1 can be cited.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 6300788 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] From the viewpoints of productivity, handling, convenience of storage, transportation, etc., it is expected that the adhesive sheet can be wound up and made into a roll. In addition, since the adhesive sheet before use (i.e., before being attached to the adherend) is sometimes processed, stored, circulated, etc. in the form of a laminated sheet laminated with a release liner for protecting the adhesive surface of the adhesive sheet, it is expected that the laminated sheet can also be made into a roll. Patent document 1 relates to a double-sided adhesive sheet wound into a roll and stored, and proposes that in order to prevent the surface of the adhesive layer from producing a plurality of tiny concave-convex (grapefruit peel-like surface), a film having a surface with high smoothness on the opposite side of the surface in contact with the adhesive layer is used as a release film attached to the first surface of the adhesive layer and a release film attached to the second surface.

[0008] However, due to the recent trend of higher definition display of display devices, the requirements for the optical homogeneity of the pressure-sensitive adhesive layer tend to be higher, and simply focusing on preventing the formation of a grapefruit-peel surface on the pressure-sensitive adhesive layer surface cannot fully meet the above requirements.

[0009] Therefore, an object of the present invention is to provide a laminated sheet including a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer has excellent optical homogeneity.

[0010] Solutions for solving problems

[0011] According to the present specification, a laminated sheet is provided, comprising: an adhesive layer, a first film laminated on a first surface of the adhesive layer, and a second film laminated on a second surface of the adhesive layer. The first film is a release film whose surface in contact with the adhesive layer, i.e., surface A, becomes a release surface. The maximum peak height Rp of the surface A of the first film is 1A The total thickness T of the first thin film and the second thin film of the laminate is less than 50 nm. SUM It is 80μm or more.

[0012] The laminated sheet of this structure is formed by making the first surface of the adhesive layer (hereinafter also referred to as "first adhesive surface") contact with Rp 1A The first adhesive surface can achieve a high degree of smoothness by making the total thickness T of the first and second films less than 50 nm. SUM When the thickness is 80 μm or more, the generation of optical distortion in the pressure-sensitive adhesive layer can be appropriately suppressed. The high smoothness of the first pressure-sensitive adhesive surface and the suppression of the generation of optical distortion can realize a laminated sheet having a pressure-sensitive adhesive layer with excellent optical homogeneity.

[0013] In the present specification, the adhesive surface refers to the surface of the adhesive layer on which the release film is laminated in the laminate sheet, that is, the surface from which the release film can be peeled off and attached to an adherend.

[0014] The laminated sheet disclosed herein can be preferably implemented in a manner that includes an adhesive layer formed of a photocurable adhesive composition as the above-mentioned adhesive layer. The photocurable adhesive composition is suitable for forming an adhesive layer with high surface smoothness. In the manner in which the photocurable adhesive composition is used in the formation of the adhesive layer, a photocurable adhesive composition that satisfies the above-mentioned T SUM It is particularly effective to suppress the occurrence of optical distortion by using a structure.

[0015] In some embodiments, the relationship between the thickness T [mm] and the elastic modulus E' [MPa] of at least one of the first film and the second film preferably satisfies the following formula: 0.10 [N·mm] < E'×T 3 The laminated sheet having such a structure can effectively suppress the occurrence of optical distortion in the pressure-sensitive adhesive layer.

[0016] In some aspects of the laminated sheet disclosed herein, the shear peeling force Fs1 of the A surface of the first film with respect to the first surface of the adhesive layer in the laminated sheet can be 0.5 N / 4 cm 2 Above and 250N / 4cm 2 The laminated sheet having the shear peeling force Fs1 within the above range can well exert the effect of suppressing the occurrence of optical distortion in the pressure-sensitive adhesive layer.

[0017] In some embodiments of the laminated sheet disclosed herein, the second film may be a peelable film whose surface in contact with the adhesive layer, i.e., surface A, becomes a peelable surface. In the laminated sheet of this embodiment, the first film is peelably laminated on the first surface of the adhesive layer, and the second film is peelably laminated on the second surface of the adhesive layer. Therefore, the adhesive layer can be grasped as a double-sided adhesive sheet in which both the first and second surfaces are adhesive surfaces. The second film preferably has a maximum peak height Rp of the surface in contact with the adhesive layer, i.e., surface A. 2A Less than 50nm. The laminated sheet of this structure is connected to Rp through the second surface (second adhesive surface) of the adhesive layer. 2A The second adhesive surface can achieve a high degree of smoothness with a release surface contact of <50nm.

[0018] As the adhesive constituting the adhesive layer, an acrylic adhesive can be preferably used. An acrylic adhesive can easily form an adhesive layer with high transparency. The high transparency of the adhesive layer can be an advantageous feature in, for example, optical applications.

[0019] The laminated sheet disclosed herein can suppress the optical distortion of the adhesive layer and easily realize a highly smooth adhesive surface, and therefore can be preferably used for the manufacture of an optical component having the above-mentioned adhesive layer. The optical component having the above-mentioned adhesive layer (hereinafter also referred to as an adhesive optical component) can be preferably manufactured by a method comprising the following steps: for example, peeling off a release film from the above-mentioned laminated sheet to expose the adhesive surface, and attaching the adhesive surface to the optical component as an adherend. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic cross-sectional view showing a laminated sheet according to one embodiment.

[0021] Figure 2 It is a schematic cross-sectional view showing a laminated sheet according to another embodiment.

[0022] Description of Reference Numerals

[0023] 10 Adhesive layer

[0024] 10a First side (first adhesive side)

[0025] 10b Second side (second adhesive side)

[0026] 21. First film (peel film)

[0027] 21a A side (peeling side)

[0028] 21b Side B

[0029] 22. Second film (peel film)

[0030] 22a Side A (peeling side)

[0031] 22b Side B

[0032] 32. Second film (support substrate)

[0033] 32a A side (non-peeling side)

[0034] 32b Side B

[0035] 40,50 layers

[0036] 42, 52 adhesive sheet

[0037] 80 core

[0038] 100, 200 rolls DETAILED DESCRIPTION

[0039] The following is a description of a suitable embodiment of the present invention. It should be noted that, in this specification, for matters other than those specifically mentioned and necessary for the implementation of the present invention, those skilled in the art can understand them based on the teachings for implementing the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, the same figure marks are sometimes used to illustrate the components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are simplified in order to clearly illustrate the present invention, and may not accurately show the size and scale of the products actually provided.

[0040] In this specification, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in a temperature range near room temperature as described above and has the property of being easily bonded to an adherend by pressure. As defined in "CADahlquist, 'Adhesion: Fundamental and Practice', McLaren & Sons, (1966) P.143", the adhesive here can generally be a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 Materials having the above properties at 25°C.

[0041] <Configuration example of laminated sheet>

[0042] The laminated sheet disclosed herein comprises: an adhesive layer, a first film laminated on the first surface of the above-mentioned adhesive layer, and a second film laminated on the second surface of the above-mentioned adhesive layer. The above-mentioned first film is a release film. Here, the release film refers to a film whose surface laminated on the adhesive layer becomes a surface (release surface) with release properties. The above-mentioned second film can be a release film or a non-release film. The laminated sheet disclosed herein exposes the adhesive surface by peeling off the release film laminated on the adhesive layer, thereby being used as an adhesive sheet. Therefore, the laminated sheet disclosed herein can also be grasped as an adhesive sheet with a release film comprising an adhesive sheet and a release film for protecting the adhesive surface of the adhesive sheet.

[0043] The structure of a laminate sheet according to one embodiment is schematically shown in Figure 1 . The laminated sheet 40 includes: an adhesive layer 10, a first film 21 laminated on the first surface 10a of the adhesive layer 10, and a second film 22 laminated on the second surface 10b of the adhesive layer. The surface (A surface) 21a of the first film 21 that contacts the adhesive layer 10 becomes a release surface. The surface (A surface) 22a of the second film 22 that contacts the adhesive layer 10 also becomes a release surface. That is, in this embodiment, the first film 21 and the second film 22 are both release films. The adhesive layer 10 contained in the laminated sheet 40 can be grasped as a double-sided adhesive sheet (substrate-free double-sided adhesive sheet) 42 that can use the first surface 10a and the second surface 10b as adhesive surfaces. Figure 1 The "10(42)" in the figure indicates that the adhesive layer 10 can also be understood as an adhesive sheet 42 including the adhesive layer. It should be noted that, in the first and second films 21 and 22, the surfaces (B surfaces) 21b and 22b on the opposite side to the A surfaces 21a and 22a can be release surfaces or non-release surfaces independently.

[0044] The first film 21 and the second film 22 may have a total thickness T SUM The maximum peak height Rp of the A surface 21a of the first film 21 is selected to be 80 μm or more. 1A The A surface 22a of the second film 22 preferably has a maximum peak height Rp of less than 50 nm, preferably less than 30 nm. 2A The thickness is less than 50 nm, and more preferably less than 30 nm. The adhesive layer 10 is formed of, for example, a photocurable adhesive composition.

[0045] The laminated sheet 40 before use is, for example, Figure 1 As shown, the laminated sheet 40 may be in the form of a roll 100 wound around a core (winding core) 80. The laminated sheet 40 may be used by peeling the first film 21 and the second film 22 from the adhesive layer 10 and attaching the exposed adhesive surfaces 10a and 10b to an adherend.

[0046] The structure of a laminate sheet according to another embodiment is schematically shown in Figure 2 . The laminated sheet 50 includes: an adhesive layer 10, a first film 21 laminated on the first surface 10a of the adhesive layer 10, and a second film 32 laminated on the second surface 10b of the adhesive layer. In this embodiment, the A surface 32a of the second film 32, that is, the surface laminated on the adhesive layer 10 becomes a non-peeling surface (non-peeling surface). The second film having a non-peeling surface laminated on the adhesive layer like this can be grasped as a supporting substrate for the adhesive layer. The adhesive layer 10 is configured to be fixed to the A surface 32a of the second film 32, that is, there is no intention to separate the adhesive layer 10 from the second film 32. On the other hand, the A surface 21a of the first film 21 and the Figure 1 The example shown is also a release surface. That is, in this embodiment, the first film is a release film and the second film 32 is a supporting substrate. As a result, the adhesive layer 10 contained in the laminated sheet 50 is integrated with the second film (supporting substrate) 32 to form a single-sided adhesive sheet 52 in which the first surface 10a can be used as an adhesive surface. It should be noted that the surface (B surface) 21b, 32b on the opposite side to the A surface 21a, 32a of the first and second films 21, 32 can be a release surface or a non-release surface independently.

[0047] The first film 21 and the second film 32 may have a total thickness T SUM The maximum peak height Rp of the A surface 21a of the first film 21 is selected to be 80 μm or more. 1A The maximum peak height Rp of the A surface 32a of the second film (support substrate) 32 is less than 50 nm, preferably less than 45 nm, and more preferably less than 40 nm. 2A In some preferred embodiments, the maximum peak height Rp of the A surface of the support substrate is 2A For example, it may be less than 50 nm, may be 45 nm or less, or may be 40 nm or less.

[0048] The laminated sheet 50 before use is, for example, Figure 2 As shown, the laminated sheet 50 may be in the form of a roll 200 wound around a core 80. The laminated sheet 50 may be used by peeling the first film 21 from the adhesive layer 10 and attaching the exposed adhesive surface 10a to an adherend.

[0049] It should be noted that Figure 1 Although the roll 100 is shown as a roll in which the laminated sheet 40 is wound around the core 80, the roll 100 may be a roll without the core 80, that is, a so-called coreless roll in which the laminated sheet 40 is wound alone. Figure 2 The same is true for the roll body 200 shown.

[0050] also, Figure 1The example shows a roll 100 in which the second film 22 is wound inside, but a roll in which the first film 21 is wound inside may also be used. Figure 2 The example shows the roll 200 in a form in which the second film (support substrate) 32 is wound inside, but the roll may be in a form in which the first film 21 is wound inside and the second film (support substrate) 32 is wound outside.

[0051] also, Figure 1 , 2 The adhesive layer 10 is illustrated as a single-layer structure, but the composition of the adhesive layer 10 is not limited thereto, and may also be a multilayer structure of more than two layers. For example, the adhesive layer may also be a composition containing two or more sub-adhesive layers composed of the same or different adhesives. In addition, the adhesive layer may also be an adhesive layer with a substrate having a non-peelable substrate built in (buried) between the first face and the second face. As substrate, plastic film, paper, nonwoven fabric, etc. may be used. From the perspective of productivity and transparency, it is preferred that an adhesive layer (substrate-free adhesive layer) not having a substrate built in between the first face and the second face is further preferred to be an adhesive layer of a single-layer structure without a substrate.

[0052] <Release film>

[0053] The first film in the laminated sheet disclosed herein is a release film whose side (A side) at least laminated on the adhesive layer becomes a release surface. The second film in the laminated sheet disclosed herein may be a release film whose side (A side) at least laminated on the adhesive layer becomes a release surface, or may be a supporting substrate whose A side becomes a non-release surface. When the second film is a release film, the second film may be a release film having the same structure as the release film used as the first film, or may be a release film having a different structure.

[0054] The maximum peak height Rp of the A surface of the release film (hereinafter also referred to as "peelable A surface") is preferably less than 50 nm. Thus, the surface of the adhesive layer (adhesive surface) that is peelably abutted against the A surface is easily smooth enough for optical applications. In addition, even in the case of, for example, a roll body formed by winding the laminated sheet, it is easy to suppress the generation of a grapefruit peel-like surface and maintain the high smoothness of the adhesive surface.

[0055] Here, in this specification, the maximum peak height (Rp) refers to the maximum peak height obtained using a contact-type surface roughness measuring device based on JIS B 0601: 2001 unless otherwise specified. As a contact-type surface roughness measuring device, for example, a stylus surface roughness measuring device "SV3100S4" manufactured by Mitutoyo Corporation or its equivalent can be used. The specific measurement operation and measurement conditions can be set according to the measurement conditions described in the embodiments described later, or set in a manner to obtain a result equivalent to or corresponding to the result obtained under the measurement conditions.

[0056] From the viewpoint of further improving the smoothness of the adhesive surface, it is advantageous that the maximum peak height Rp of the peelable A surface is below 45nm, preferably below 40nm, below 35nm, or below 30nm. In some embodiments, the maximum peak height Rp of the peelable A surface can be below 25nm, below 20nm, or less than 20nm. The lower limit of the maximum peak height Rp of the peelable A surface is not particularly limited. From the viewpoint of improving the smoothness of the adhesive surface, the smaller the maximum peak height Rp of the peelable A surface, the more preferred. On the other hand, from the viewpoint of cost and productivity, in some embodiments, the maximum peak height Rp of the peelable A surface can be, for example, above 2nm, above 5nm, above 10nm, above 15nm, or above 20nm. Examples of suitable forms of the laminated sheet disclosed herein may include: a form in which the maximum peak height Rp of the peelable A surface is greater than or equal to 20 nm and less than 50 nm, a form in which it is greater than or equal to 20 nm and less than 30 nm, a form in which it is greater than or equal to 5 nm and less than 50 nm, a form in which it is greater than or equal to 5 nm and less than 30 nm, a form in which it is greater than or equal to 5 nm and less than 20 nm, etc.

[0057] In the embodiment where both the first and second films are release films, at least one of the first and second films preferably satisfies the upper limit, lower limit or numerical range of the maximum peak height Rp of any release surface A, and more preferably both the first and second films satisfy the above-mentioned upper limit, lower limit or numerical range.

[0058] In the case where both the first and second films are release films, the maximum peak height Rp of the A surface of the second film 2A The maximum peak height Rp of the A surface of the first film can be 1A In some embodiments, Rp 1A With Rp 2A The absolute value of the difference (i.e. |Rp 1A -Rp 2A |) For example, it may be about 20 nm or less, and from the viewpoint of more efficiently improving the optical homogeneity of the pressure-sensitive adhesive layer, it is preferably about 10 nm or less, and more preferably about 5 nm or less.

[0059] The release film used as the first film and / or the second film is not particularly limited and can be appropriately selected according to the purpose. Non-limiting examples of the release film that can be used include: a release film having a release treatment layer on the surface of the release film substrate; a release film formed of a fluorine-based polymer (polytetrafluoroethylene, etc.), a polyolefin-based resin (polyethylene, polypropylene, etc.) and a low-adhesive resin; etc. In some embodiments, a release film having a release treatment layer on a release film substrate can be preferably used.

[0060] As the release film substrate, various plastic films can be used. In this specification, the plastic film is typically a non-porous sheet material, and is a concept distinguished from (that is, excluding) non-woven fabrics, for example.

[0061] Examples of the material of the plastic film include polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin resins such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, and ethylene-butene copolymers; cellulose polymers such as cellulose diacetate and cellulose triacetate (TAC); acetate resins; polycarbonate (PC); nylon 6, nylon 66, and partially aromatic polyamides; Polyamide (PA); polyimide such as transparent polyimide (CPI); polyamide-imide (PAI); polyetheretherketone (PEEK); polysulfone resin; polyethersulfone (PES) resin; cyclic polyolefins such as norbornene resin; (meth)acrylic resin; polyvinyl chloride resin; polyvinylidene chloride resin; polystyrene resin; polyvinyl alcohol (PVA) resin; ethylene-vinyl acetate copolymer (EVA); ethylene-vinyl alcohol copolymer; polyarylate resin; polyphenylene sulfide (PSS), etc. A release film substrate formed of any one of these resins or a mixture of two or more thereof can be used. As a preferred release film substrate, a polyester resin film (e.g., PET film) formed of a polyester resin can be cited.

[0062] The release treatment layer can be a release treatment layer formed by surface treating the release film substrate as described above with a release treatment agent. The release treatment agent can be a known release treatment agent such as a silicone release treatment agent, a long-chain alkyl release treatment agent, a fluorine release treatment agent, molybdenum (IV) sulfide, etc. The thickness and formation method of the release treatment layer are not particularly limited, and can be set in a manner that exerts the desired release property on the A surface of the release film. Although not particularly limited, the thickness of the release treatment layer is usually appropriate to be 0.01 μm or more, preferably 0.05 μm or more, or 0.08 μm or more. In addition, the thickness of the release treatment layer can be, for example, 3 μm or less, 1 μm or less, or 0.5 μm or less. As a method for forming a release treatment layer on a release film, a method of imparting a release treatment agent to a release film substrate and curing it (drying, crosslinking, reaction, etc.), a method of laminating a pre-made release treatment layer on a release film substrate, a method of co-extruding a release film substrate or its forming material with a release treatment agent, etc., can be exemplified, but it is not limited thereto.

[0063] As a suitable example of the above-mentioned release treatment agent, a silicone-based release treatment agent can be cited. The silicone-based release treatment agent used can be in any form such as solvent-based, solvent-free, aqueous (aqueous solution type, water-dispersible type), etc. In some embodiments, from the perspective of ease of viscosity adjustment and easy formation of a highly homogeneous release treatment layer, a solvent-based silicone-based release treatment agent can be preferably used.

[0064] The silicone-based release agent may be any type of addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, etc. From the viewpoint of reactivity, performance stability, etc., addition reaction type silicone-based release agents can be preferably used in some aspects.

[0065] The addition reaction type silicone release agent generally comprises organohydrogenpolysiloxane and organopolysiloxane having an aliphatic unsaturated group, and may be either solvent-free or solvent-based. For example, a heat-curable addition reaction type silicone release agent that is crosslinked and cured by a thermal addition reaction can be preferably used.

[0066] As a heat-curable addition reaction type silicone release agent, for example, the following release agent can be used, which includes: a polysiloxane having a hydrogen atom (H) bonded to a silicon atom (Si) in the molecule (Si-H group-containing polysiloxane), and a polysiloxane containing a functional group (Si-H group-reactive functional group) reactive to a Si-H bond (covalent bond of Si and H) in the molecule (Si-H group-reactive polysiloxane). The release agent is crosslinked by an addition reaction between the Si-H group and the Si-H group-reactive functional group to cure.

[0067] In the above-mentioned Si-H group-containing polysiloxane, the Si bonded with H can be any of Si in the main chain and Si in the side chain. Preferably, the polysiloxane contains two or more Si-H groups in the molecule. As the polysiloxane containing two or more Si-H groups, dimethyl hydrogen siloxane polymers such as poly (dimethylsiloxane-methylsiloxane) can be listed.

[0068] On the other hand, as the above-mentioned Si-H-based reactive polysiloxane, a polysiloxane in which a Si-H-based reactive functional group or a side chain containing the functional group is bonded to Si (e.g., Si at the end of the main chain, Si inside the main chain) forming the main chain (skeleton) of the siloxane-based polymer can be used. Among them, a polysiloxane in which a Si-H-based reactive functional group is directly bonded to Si in the main chain is preferred. In addition, a polysiloxane containing two or more Si-H-based reactive functional groups in the molecule is preferred. As the Si-H-based reactive functional group, for example, alkenyl groups such as vinyl and hexenyl can be listed.

[0069] Examples of the siloxane polymer forming the main chain include polydialkylsiloxanes (the two alkyl groups may be the same or different) such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane; polyalkylarylsiloxane; polymers obtained by polymerizing a plurality of Si-containing monomers such as poly(dimethylsiloxane-methylsiloxane); etc. As a particularly suitable main chain polymer, polydimethylsiloxane may be mentioned.

[0070] In some embodiments, the following heat-curable addition reaction type silicone release agent can be preferably used, the release agent containing: a polysiloxane containing two or more Si-H groups in the molecule, and a polysiloxane containing two or more Si-H group reactive functional groups in the molecule. The mixing ratio of the Si-H group-containing polysiloxane and the Si-H group reactive polysiloxane contained in the above release agent is not particularly limited as long as the release agent is sufficiently cured to achieve the above silicone transfer amount. It is preferably selected in a manner that the molar number X of Si in the Si-H group and the molar number Y of the Si-H group reactive functional group are X≥Y, and it is generally preferred that X:Y be about 1:1 to 2:1 (more preferably 1.2:1 to 1.6:1).

[0071] The addition reaction type silicone-based release treatment agent may also contain a catalyst for accelerating the crosslinking reaction. Examples of the catalyst include platinum-based catalysts such as platinum particles, chloroplatinic acid and its derivatives. The amount of the catalyst added is not particularly limited, and is selected, for example, from a range of preferably 0.1 to 1000 ppm (more preferably 1 to 100 ppm) relative to the Si-H-based reactive polysiloxane.

[0072] As the silicone-based release agent, a product prepared or obtained by mixing the above-mentioned components or a commercial product containing the above-mentioned components can be used. In addition, in addition to the above-mentioned components, other known and commonly used additives such as fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, colorants (dyes, pigments, etc.) can be appropriately added as needed.

[0073] In several other embodiments, a release film having a release treatment layer based on a long-chain alkyl release treatment agent may be preferably used. As the long-chain alkyl release treatment agent, for example, polyethylene carbamate obtained by reacting a polyvinyl alcohol polymer with a long-chain (e.g., carbon number 8 to 30) alkyl isocyanate, alkyl urea derivatives obtained by reacting polyethylene imine with a long-chain (e.g., carbon number 8 to 30) alkyl isocyanate, etc. may be used. In addition, a long-chain alkyl release treatment agent containing a long-chain alkyl material described in Japanese Patent Application Publication No. 2016-145341 may be used as a release treatment agent for the release film used in the laminated sheet disclosed herein. It should be noted that the above-mentioned Japanese Patent Application Publication No. 2016-145341 is incorporated into this specification by reference.

[0074] The silicone-based release agent can be preferably used, for example, to prepare a release film having a maximum peak height Rp of the release surface A in the range of 20 nm to less than 50 nm, 20 nm to 40 nm, 20 nm to 30 nm, etc., but is not limited thereto. Non-silicone-based release agents such as long-chain alkyl-based release agents can be used, for example, to prepare a release film having a maximum peak height Rp of the release surface A in the range of 20 nm to less than 50 nm, 20 nm to 40 nm, 20 nm to 30 nm, etc., or can be preferably used, for example, to prepare a release film having a maximum peak height Rp of the release surface A in the range of 5 nm to less than 50 nm, 5 nm to 30 nm, 5 nm to less than 25 nm, 10 nm to less than 25 nm, 15 nm to less than 30 nm, 15 nm to less than 25 nm, etc., but is not limited thereto.

[0075] In some embodiments of the laminated sheet disclosed herein, the release film included in the laminated sheet is preferably configured so that the residual adhesion rate of the A surface (release surface) measured by the following method is 60% or more (more preferably 70% or more, and further preferably 80% or more). The residual adhesion rate of the A surface of the release film is typically 100% or less, and may be 95% or less, or 90% or less from a practical point of view such as cost and productivity.

[0076] (Method for measuring residual adhesion)

[0077] Under the environment of 23°C and 50% RH, a 2 kg roller was reciprocated once, and a product name "NO.31B" (a polyester-based adhesive tape manufactured by Nitto Denko Corporation, with a width of 19 mm) was attached to a stainless steel plate. After being left for 30 minutes under the environment of 23°C and 50% RH, the stress when the adhesive tape was peeled off 50 mm under the conditions of a peeling angle of 180° and a tensile speed of 300 mm / min using a tensile testing machine was measured. The maximum stress value at this time was read and used as the peel strength (F) of the control. R0 )[N / 19mm].

[0078] In addition, under an environment of 23°C and 50% RH, a 5kg roller was reciprocated once to adhere the product name "NO.31B" (a polyester-based adhesive tape manufactured by Nitto Denko Corporation, with a width of 19mm) to the A side of the peeling film of the measurement object, and the film was heat-treated in a hot air dryer at 70°C with a load of 5kg for 24 hours, and then placed in an environment of 23°C and 50% RH for 2 hours. Thereafter, the adhesive tape (product name "NO.31B") was peeled off from the A side of the peeling film of the measurement object, and the adhesive tape was adhered to a stainless steel plate by reciprocating a 2kg roller once, and placed in an environment of 23°C and 50% RH for 30 minutes, and then the stress was measured when the adhesive tape was peeled off 50mm under the same environment using a tensile tester at a peeling angle of 180° and a tensile speed of 300mm / min, and the maximum stress value at this time was read, and the maximum stress value was taken as the residual peel strength (F R1 )[N / 19mm].

[0079] Then, using the above residual peel strength (F R1 ) and the peel strength of the above control (F R0 ), and the residual adhesion rate [%] was calculated by the following formula.

[0080] Residual bonding rate [%] = (F R1 / F R0 )×100

[0081] The release film with a high residual adhesion rate tends to have good unwinding properties from a roll. This is particularly meaningful for a release film with a low maximum peak height Rp of the A surface (e.g., less than 45 nm, less than 35 nm, or less than 30 nm). The residual adhesion rate can be adjusted, for example, by selecting a release agent used in the formation of a release treatment layer constituting the A surface of the release film. When a silicone release agent is used, it is preferred to select a non-transferring silicone release agent.

[0082] <Supporting base material>

[0083] In some embodiments of the laminate disclosed herein, the second film may be a non-peelable film, i.e., a supporting substrate, which is the surface in contact with the adhesive layer, i.e., the A surface. As the supporting substrate, various plastic films may be used. The material constituting the plastic film may be arbitrarily selected from the same materials as the materials exemplified for the plastic film that can be used as a peeling film substrate. As preferred plastic films, polyester resin films such as PET films, cellulose diacetate films, cellulose triacetate (TAC) films, polyimide resin films such as transparent polyimide (CPI) films, and polyethersulfone (PES) resin films may be exemplified. A plastic film having transparency is preferred. The A surface of the supporting substrate may be subjected to surface treatments such as primer coating, corona discharge treatment, and plasma treatment. Such surface treatment may help to improve the adhesion between the A surface and the adhesive layer.

[0084] In the technology disclosed herein, the plastic film used as the above-mentioned supporting substrate or release film substrate may be any of a non-stretched film, a uniaxially stretched film, and a biaxially stretched film. In addition, the above-mentioned plastic film may be a single-layer structure or a multilayer structure (e.g., a three-layer structure) containing two or more sublayers. The above-mentioned plastic film may be mixed with antioxidants, anti-aging agents, heat stabilizers, light stabilizers, ultraviolet absorbers, pigments, dyes and other colorants, lubricants, fillers, antistatic agents, nucleating agents and other known additives that can be used in the supporting substrate or release film substrate of the adhesive sheet. In the plastic film with a multilayer structure, each additive may be mixed in all sublayers or only in a part of the sublayers.

[0085] The Rp of the A surface of the supporting substrate is not particularly limited. The maximum peak height Rp of the A surface of the supporting substrate is usually appropriate to be less than 300nm, preferably less than 150nm. From the viewpoint of improving the transparency of the adhesive sheet containing the supporting substrate, in some embodiments, the maximum peak height Rp of the A surface of the supporting substrate is, for example, less than 50nm, preferably less than 45nm, can be less than 40nm, can be less than 35nm, can be less than 30nm, can be less than 25nm, or can be less than 20nm. In addition, from the viewpoint of cost and productivity, in some embodiments, the maximum peak height Rp of the A surface of the supporting substrate can be, for example, more than 2nm, can be more than 5nm, can be more than 10nm, or can be more than 15nm. The Rp of the A surface of the supporting substrate (the second film) can be the same degree or different from the Rp of the A surface of the peeling film (the first film).

[0086] <First and second films>

[0087] In the laminated sheet disclosed herein, the total thickness T of the first film and the second film is SUMPreferably it is 80 μm or more. With this configuration, it is possible to suppress the phenomenon of optical distortion of the adhesive layer and thereby improve the optical homogeneity of the adhesive layer. The reason for obtaining such an effect is not particularly restrictive, and for example, it can be considered as follows. That is, when shrinkage due to drying and curing occurs when the adhesive layer is formed from a liquid adhesive composition, if the degree of shrinkage varies depending on the position, the deviation (unevenness) is observed as an optical distortion of the adhesive layer. In addition, due to the deformation when the laminated sheet is wound to form a roll and when the laminated sheet is unwound from the roll, a stress of elongation or contraction along the surface direction is applied to the adhesive layer, thereby causing uneven expansion and contraction of the adhesive layer, thereby also causing optical distortion of the adhesive layer. With the laminated sheet disclosed herein, by making the total thickness T of the first and second films SUM By setting the above value, the rigidity of the laminated sheet as a whole can be improved, thereby appropriately restricting the free expansion and contraction of the adhesive layer sandwiched between the first and second films, thereby suppressing the expansion and contraction unevenness of the adhesive layer (making the expansion and contraction degree uniform) and suppressing the occurrence of optical distortion.

[0088] When an adhesive layer is formed from an active energy ray-curable adhesive composition, curing shrinkage is generally large, and therefore optical distortion is easily caused by deviation in curing shrinkage when forming the adhesive layer. SUM The above-mentioned effect of suppressing the uneven expansion and contraction of the adhesive layer can be particularly well exerted when the adhesive layer is formed by a method of curing a liquid film of the adhesive composition between the A surfaces of the first film and the second film. Therefore, the laminated sheet disclosed herein can be particularly preferably implemented in a manner having an adhesive layer formed of a solvent-free or active energy ray-curable adhesive composition (e.g., a solvent-free active energy ray-curable adhesive composition).

[0089] From the viewpoint of better exerting the effect of suppressing the generation of optical distortion, in some embodiments, the total thickness T of the first and second films is SUM The thickness T is preferably 90 μm or more, more preferably 100 μm or more, and may be 110 μm or more, 120 μm or more, or 140 μm or more. SUM There is no particular upper limit on the thickness T. SUM Generally, it is appropriate to have a thickness of 1000 μm or less, preferably 800 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 180 μm or less, or 160 μm or less. The laminated sheet disclosed herein may also have a thickness T SUMThe thickness is 135 μm or less, 125 μm or less, or 115 μm or less.

[0090] The thickness of the first film may be in relation to the thickness of the second film. SUM The thickness of the first film can be selected from a range of 80 μm or more, for example, 2 μm to 500 μm or so. From the perspective of the handling of the first film during the manufacture and use of the laminated sheet, it is advantageous for the thickness of the first film to be 5 μm or more, preferably 10 μm or more, and more preferably 25 μm or more. From the perspective of better suppressing the optical distortion of the adhesive layer, in some embodiments, the thickness of the first film is preferably 35 μm or more, more preferably 40 μm or more, 45 μm or more, 50 μm or more, 60 μm or more, or 70 μm or more. In addition, from the perspective of avoiding the thickness of the laminated sheet to be greater than the required thickness, the thickness of the first film is usually 300 μm or less, preferably 250 μm or less, 200 μm or less, 190 μm or less, 150 μm or less, 130 μm or less, 110 μm or less, 90 μm or less, or 80 μm or less.

[0091] The thickness of the second film may be in relation to the thickness of the first film. SUM The method of selecting a thickness of 80 μm or more is not particularly limited. The thickness of the second film can be selected from a range of, for example, about 2 μm to 500 μm. From the same point of view as the first film, the thickness of the second film is advantageously 5 μm or more, preferably 10 μm or more, and more preferably 25 μm or more. In some embodiments, it is preferably 35 μm or more, more preferably 40 μm or more, 45 μm or more, 50 μm or more, 60 μm or more, or 70 μm or more. In addition, the thickness of the second film is usually appropriate to be 300 μm or less, preferably 250 μm or less, 200 μm or less, 190 μm or less, 150 μm or less, 130 μm or less, 110 μm or less, 90 μm or less, or 80 μm or less.

[0092] In some embodiments of the laminated sheet disclosed herein, from the viewpoint of suppressing optical distortion, the thickness of the first and second films may be both 25 μm or more (preferably both 35 μm or more, more preferably both 50 μm or more, and further preferably both 70 μm or more). In addition, from the viewpoint of avoiding the thickness of the laminated sheet to be greater than the required thickness, in some embodiments, the thickness of the first and second films may be both 200 μm or less (preferably both 150 μm or less, more preferably both 150 μm or less, and further preferably both 100 μm or less).

[0093] The thickness of the first film and the thickness of the second film may be the same or different. When the thickness of the first and second films are different, the relationship between their thicknesses may be first film < second film or second film < first film.

[0094] In some embodiments of the laminated sheet disclosed herein, at least one of the first and second films (preferably both) may have a thickness T [mm] and an elastic modulus E' [MPa] that satisfies the following equation: 0.10 [N·mm] < E' × T 3 The above E'×T 3 The value of is proportional to the bending rigidity of the film. Therefore, the E'×T 3 When the value of is large, it means that the bending rigidity of the film is high. By using a film with higher bending rigidity, the free expansion and contraction of the adhesive layer in contact with the film can be restricted, thereby better suppressing the occurrence of expansion and contraction unevenness.

[0095] Here, the elastic modulus E' of the film can be measured using a commercially available dynamic viscoelasticity measuring device. Specifically, the sample (first film or second film) to be measured is cut into a strip with a length of 30 mm and a width of 5 mm to prepare a test piece. For the test piece, a dynamic viscoelasticity measuring device (manufactured by TA Instruments, RSA-III) is used to measure the tensile storage modulus in the temperature range of 0°C to 100°C under the conditions of a distance between chucks of 23 mm, a heating rate of 10°C / min, a frequency of 1Hz, and a strain of 0.05% in a tensile measurement mode, and the obtained value is used as the elastic modulus E' of the film.

[0096] In some embodiments, at least one of the first and second films (preferably both) has an E'×T 3 The value of can be, for example, 0.12 N·mm or more, 0.15 N·mm or more, 0.20 N·mm or more, 0.25 N·mm or more, 0.30 N·mm or more, 0.50 N·mm or more, 0.70 N·mm or more, or 0.90 N·mm or more. 3A larger adhesive sheet can better suppress the optical distortion of the adhesive layer. The laminated sheet disclosed herein can also be made of at least one of the first and second films (preferably both) with an E'×T 3 It is preferably implemented in an embodiment of 2.0 N·mm or more, 3.0 N·mm or more, or 4.0 N·mm or more. 3 The upper limit of is not particularly limited. From the viewpoint of the handling properties of the film and the laminated sheet containing the film, it is usually appropriate to be about 100 N·mm or less, preferably about 50 N·mm or less (for example, 20 N·mm or less). From the viewpoint of avoiding the thickness of the laminated sheet to be greater than the required thickness, in some embodiments, E'×T in the first and second films is 3 The E'×T of the film with a larger value 3 The value of may be, for example, 10 N·mm or less, 7 N·mm or less, 5 N·mm or less, or 3 N·mm or less.

[0097] E'×T of the first film 3 E'×T of the second film 3 The laminate sheet disclosed herein may be such that the release film (in the embodiment where both the first and second films are release films, both the first and second films) contained in the laminate sheet satisfies any of the above E'×T 3 The method is preferably implemented.

[0098] The elastic modulus E' of each film is not particularly limited, and may be, for example, 300 MPa or more, or 500 MPa or more. 3 From the viewpoint of the elastic modulus E' of the film, in some embodiments, the elastic modulus E' of the film is preferably, for example, 1000 MPa or more, more preferably 1500 MPa or more (for example, 2000 MPa or more). The upper limit of E' is not particularly limited. From the viewpoint of ease of acquisition and ease of manufacture, it is appropriate that the E' of the film is usually 30000 MPa or less, preferably 20000 MPa or less, more preferably 10000 MPa or less (for example, 6000 MPa or less). The elastic modulus E' of the film can be adjusted according to the composition of the film, the materials used, their combination, etc.

[0099] In the laminated sheet disclosed herein, the surface opposite to the A surface of the first and second films (hereinafter also referred to as "B surface") can be a release surface or a non-release surface independently. The maximum peak height Rp of the B surface is not particularly limited. The maximum peak height Rp of the B surface can be the same as the maximum peak height Rp of the A surface, or it can be different. For films in which the maximum peak height Rp of the A surface and the B surface are different, the relationship of the maximum peak height Rp can be A surface < B surface, or B surface < A surface.

[0100] In some embodiments, the maximum peak height Rp of the B surface can be, for example, less than 50 nm, less than 45 nm, less than 40 nm, less than 35 nm, less than 30 nm, less than 25 nm, less than 20 nm, or less than 20 nm. A film with a smaller maximum peak height Rp of the B surface is advantageous from the perspective of productivity and ease of obtaining the film because the maximum peak height Rp between the A surface and the B surface is not significantly different. The lower limit of the maximum peak height Rp of the B surface is not particularly limited. From the perspective of cost and ease of manufacturing, it can be, for example, more than 2 nm, more than 5 nm, more than 10 nm, more than 15 nm, or more than 20 nm.

[0101] In other embodiments, the maximum peak height Rp of the B surface can be, for example, 50 nm or more, 100 nm or more, 200 nm or more, 350 nm or more, 450 nm or more, or 550 nm or more. A film having a large maximum peak height Rp of the B surface is advantageous from the viewpoint of handling due to the slipperiness of the B surface. The upper limit of the maximum peak height Rp of the B surface is not particularly limited, and from the viewpoints of cost, ease of acquisition, etc., it can be, for example, less than 2000 nm, less than 1500 nm, less than 1000 nm, less than 800 nm, less than 600 nm, less than 500 nm, or less than 450 nm.

[0102] The first and second films may both be films with a smaller maximum peak height Rp on the B surface, or both be films with a larger maximum peak height Rp on the B surface, or one may be a film with a smaller maximum peak height Rp on the B surface, and the other may be a film with a larger maximum peak height Rp on the B surface. The relationship between Rp of the B surface of the first film and Rp of the B surface of the second film is not particularly limited. The maximum peak height Rp of the B surface of the second film may be the same as or different from the maximum peak height Rp of the B surface of the first film. In a laminated sheet in which the maximum peak height Rp of the B surface of the first film is different from that of the second film, the relationship between the maximum peak height Rp of the B surface of the first and second films may be that the first film is less than the second film, or the second film is less than the first film.

[0103] <Adhesive layer>

[0104] In the technology disclosed herein, the type of adhesive constituting the adhesive layer contained in the laminated sheet is not particularly limited. The above-mentioned adhesive layer can be an adhesive layer composed of one or more adhesives selected from various known adhesives such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, their mixed systems, etc.), silicone adhesives, polyester adhesives, polyurethane adhesives, polyether adhesives, polyamide adhesives, fluorine adhesives, etc. Here, acrylic adhesives refer to adhesives with acrylic polymers as base polymers (the main component in the polymer component, i.e., the component with a content greater than 50% by weight). The meaning of rubber adhesives and other adhesives is also the same. As a preferred adhesive layer from the viewpoints of transparency, weather resistance, etc., it can be listed that the content of acrylic adhesives is more than 50% by weight, more preferably more than 70% by weight, and more preferably more than 90% by weight. The content of acrylic adhesives can be greater than 98% by weight, or it can be an adhesive layer basically composed of acrylic adhesives.

[0105] Here, in this specification, "(meth)acrylic acid" means including acrylic acid and methacrylic acid. Similarly, "(meth)acryloyl" means including acryloyl and methacryloyl, and "(meth)acrylate" means including acrylate and methacrylate.

[0106] In addition, in this specification, an acrylic polymer refers to a polymer containing a (meth)acrylic monomer as a monomer component constituting the acrylic polymer. In other words, it refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer. Here, a (meth)acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule.

[0107] Although not particularly limited, in one embodiment of the technology disclosed herein, the above-mentioned adhesive layer can be suitably prepared using an adhesive composition containing monomer components constituting an acrylic polymer. Hereinafter, such an adhesive composition is sometimes referred to as an "acrylic adhesive composition". Here, "monomer components constituting an acrylic polymer" refers to monomer components constituting an acrylic polymer in an adhesive obtainable from the acrylic adhesive composition. The above-mentioned monomer components can be included in the acrylic adhesive composition as unreacted monomers (i.e., in the form of raw monomers in which the polymerized functional groups are unreacted), can be included in the acrylic adhesive composition in the form of a polymer (i.e., as a monomer unit), or can be included in the acrylic adhesive composition in both forms.

[0108] <Monomer ingredients>

[0109] In one embodiment of the technology disclosed herein, the adhesive layer can be formed using an adhesive composition containing the following (A) component as a monomer component constituting the acrylic polymer. In a preferred embodiment, the adhesive layer can be suitably formed using an acrylic adhesive composition containing at least the following (A) component and, if necessary, further containing one or both of the following (B) component and the following (C) component as monomer components constituting the acrylic polymer.

[0110] ((A) ingredient)

[0111] The component (A) is an alkyl (meth)acrylate having an alkyl group with 2 to 18 carbon atoms at the ester terminal. Hereinafter, an alkyl (meth)acrylate having an alkyl group with a carbon number of not less than X and not more than Y at the ester terminal may be referred to as “alkyl (meth)acrylate C X-Y Alkyl esters". (Meth) acrylic acid C 2-18 C in alkyl esters 2-18 The structure of the alkyl group is not particularly limited, and both a linear structure and a branched structure of the alkyl group can be used. As component (A), such (meth)acrylic acid C can be used alone. 2-18 Among the alkyl esters, one kind or two or more kinds are used in combination.

[0112] As (meth)acrylic acid C having a linear alkyl group at the ester terminal 2-18 Alkyl esters include ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, n-pentadecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-heptadecyl (meth)acrylate, and n-octadecyl (meth)acrylate. In addition, as the (meth)acrylate C having a branched alkyl group at the ester end, 3-18The alkyl esters include isopropyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, isopentyl (meth)acrylate, tert-amyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, 2-propylheptyl (meth)acrylate, isondecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isostearyl (meth)acrylate, and the like. The technology disclosed herein can preferably be prepared in such a manner that component (A) contains an alkyl ester selected from acrylic acid C 4-9 One or more of the alkyl esters are used. 4-9 Preferred examples of the alkyl ester include n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, and isononyl acrylate.

[0113] ((B) ingredient)

[0114] The component (B) is a monomer selected from the group consisting of alicyclic monomers and heterocyclic monomers. The component (B) is typically used in combination with the component (A) and can contribute to improving the cohesiveness, transparency, heat resistance, etc. of the adhesive.

[0115] As the alicyclic monomer, an alicyclic monomer having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having an alicyclic structure-containing group can be used without particular limitation. The alicyclic monomer can be used alone or in combination of two or more. Here, "alicyclic structure-containing group" refers to a portion containing at least one alicyclic structure. In addition, "alicyclic structure" refers to a saturated or unsaturated carbon ring structure that is not aromatic. In this specification, the alicyclic structure-containing group is sometimes referred to as an "alicyclic group". As preferred examples of the alicyclic group, hydrocarbon groups and hydrocarbonoxy groups containing alicyclic structures can be listed.

[0116] Examples of preferred alicyclic monomers in the technology disclosed herein include alicyclic (meth)acrylates having an alicyclic group and a (meth)acryloyl group. Specific examples of alicyclic (meth)acrylates include cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, and the like, and HPMPA, TMA-2, HCPA, and the like shown in the following chemical formula may also be cited.

[0117]

[0118] The number of carbon atoms in the alicyclic group (in the case of alicyclic (meth)acrylate, the portion obtained by removing the (meth)acryloyl group from the alicyclic (meth)acrylate) in the alicyclic monomer is not particularly limited. For example, an alicyclic monomer having 4 to 24 carbon atoms (preferably 5 to 18, more preferably 5 to 12) in the alicyclic group can be used. Among them, cyclohexyl acrylate (CHA), cyclohexyl methacrylate, isobornyl acrylate (IBXA), and isobornyl methacrylate are preferred, CHA and IBXA are more preferred, and CHA is particularly preferred.

[0119] Examples of heterocyclic monomers include cyclic nitrogen-containing monomers and cyclic ether-containing monomers. Similar to alicyclic monomers, heterocyclic monomers can contribute to the improvement of the aggregation, transparency, and heat resistance of the adhesive. In addition, they can also contribute to the improvement of the adhesive strength and cohesive force. The heterocyclic monomers can be used alone or in combination of two or more.

[0120] As the cyclic nitrogen-containing monomer, a monomer having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a cyclic nitrogen structure can be used without particular limitation. The cyclic nitrogen structure preferably has a nitrogen atom in the cyclic structure. As the cyclic nitrogen-containing monomer, for example, lactam-based vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; oxazoline-containing monomers such as 2-vinyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, and 2-isopropenyl-2-oxazoline; vinyl monomers having nitrogen-containing heterocycles such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, and vinylmorpholine, etc. As other examples of cyclic nitrogen-containing monomers, (meth)acrylic monomers containing nitrogen-containing heterocycles such as morpholine rings, piperidine rings, pyrrolidine rings, piperazine rings, and aziridine rings can be listed. Specific examples include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, N-acryloylaziridine, etc. Among the above cyclic nitrogen-containing monomers, lactam-based vinyl monomers are preferred, and N-vinylpyrrolidone is more preferred, from the viewpoint of aggregation properties.

[0121] As a monomer having a cyclic ether group, a monomer having a polymerizable functional group containing an unsaturated double bond such as a (meth) acryloyl group or a vinyl group and having a cyclic ether group such as an epoxy group or an oxetane group can be used without particular limitation. As an epoxy group-containing monomer, for example, glycidyl (meth) acrylate, 3,4-epoxycyclohexyl methyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate glycidyl ether, etc. can be listed. As an oxetane-containing monomer, for example, 3-oxetane methyl (meth) acrylate, 3-methyl-oxetane methyl (meth) acrylate, 3-ethyl-oxetane methyl (meth) acrylate, 3-butyl-oxetane methyl (meth) acrylate, 3-hexyl-oxetane methyl (meth) acrylate, etc. can be listed.

[0122] ((C) ingredient)

[0123] The component (C) is a monomer having at least one of a hydroxyl group and a carboxyl group.

[0124] As a hydroxyl-containing monomer, a monomer having a polymerizable functional group containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a hydroxyl group can be used without particular limitation. Hydroxyl-containing monomers can be used alone or in combination of two or more. As hydroxyl-containing monomers, for example: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and other hydroxyalkyl (meth)acrylates; [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate and other hydroxyalkyl (meth)acrylate cycloalkyls. In addition, hydroxyethyl (meth)acrylamide, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether and the like can also be cited. Among them, hydroxyalkyl (meth)acrylates are preferred. For example, a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 6 carbon atoms can be preferably used. In a preferred embodiment, one or more selected from 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate, 4-hydroxybutyl acrylate (4HBA) and 4-hydroxybutyl methacrylate can be used as the hydroxyl-containing monomer. The hydroxyl-containing monomer used in a suitable embodiment of the technology disclosed herein can be 4HBA alone, HEA alone, or a combination of 4HBA and HEA.

[0125] As the carboxyl-containing monomer, a monomer having a polymerizable functional group containing an unsaturated double bond such as a (meth)acryloyl group, a vinyl group, and a carboxyl group can be used without particular limitation. One type of the carboxyl-containing monomer can be used alone or two or more types can be used in combination. Examples of carboxyl-containing monomers include: ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate; ethylenically unsaturated dicarboxylic acids such as itaconic acid, maleic acid, fumaric acid, and citraconic acid; their metal salts (such as alkali metal salts); anhydrides of the above-mentioned ethylenically unsaturated dicarboxylic acids such as maleic anhydride and itaconic anhydride, etc. Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred.

[0126] The technology disclosed herein can be preferably implemented in a manner that the (C) component contains a hydroxyl-containing monomer. That is, it is preferred that the (C) component contains only a hydroxyl-containing monomer, or contains a hydroxyl-containing monomer and a carboxyl-containing monomer. In the case where the (C) component contains a hydroxyl-containing monomer and a carboxyl-containing monomer, the proportion of the hydroxyl-containing monomer in the entire (C) component is preferably greater than about 50% by weight, and more preferably about 80% by weight or more (for example, about 90% by weight or more). From the viewpoint of reducing metal corrosion caused by carboxyl groups, it is preferred to make the proportion of the hydroxyl-containing monomer in the (C) component more. The technology disclosed herein can be preferably implemented in a manner that the monomer component does not substantially contain a carboxyl-containing monomer. For example, the proportion of the carboxyl-containing monomer in the monomer component can be set to be less than about 1% by weight, preferably less than about 0.5% by weight, and more preferably less than about 0.2% by weight.

[0127] The proportion of the above-mentioned (A) component in the overall monomer component is not particularly limited. From the viewpoint of imparting appropriate aggregation to the adhesive, the proportion of the above-mentioned (A) component is generally about 90% by weight or less, preferably about 85% by weight or less, and more preferably about 75% by weight or less. In a preferred embodiment, the proportion of the above-mentioned (A) component can be set to about 70% by weight or less (more preferably about 60% by weight or less, and further about 50% by weight or less, for example about 45% by weight or less). In addition, from the viewpoint of initial adhesion to the adherend, the proportion of the above-mentioned (A) component is preferably about 30% by weight or more, and more preferably about 35% by weight or more. In one embodiment, the proportion of the (A) component in the overall monomer component can be set to, for example, about 30 to 75% by weight.

[0128] In the case where the above-mentioned monomer component contains (B) component, the proportion of (B) component in the whole monomer component is not particularly limited. Considering the balance of adhesive properties, it is appropriate that the proportion of the above-mentioned (B) component is usually about 3% by weight or more, preferably about 5% by weight or more, more preferably about 8% by weight or more, and can also be about 10% by weight or more. In addition, from the viewpoint of the initial adhesion to the adherend, it is appropriate that the proportion of the above-mentioned (B) component is about 65% by weight or less, preferably about 60% by weight or less, more preferably about 55% by weight or less (and then about 50% by weight or less, for example, about less than 50% by weight). In a preferred embodiment, the proportion of (B) component in the whole monomer component can be set to about 15% by weight or more, or about 20% by weight or more, or about 25% by weight or more, or about 30% by weight or more (for example, about 35% by weight or more). In one embodiment, the proportion of (B) component in the whole monomer component can be set to, for example, about 20 to 50% by weight.

[0129] When the above-mentioned monomer component contains component (C), the proportion of component (C) in the whole monomer component is not particularly limited. From the viewpoint of initial adhesion to the adherend, the proportion of the above-mentioned component (C) is typically about 3% by weight or more, preferably about 5% by weight or more, and more preferably about 8% by weight or more (for example, about 10% by weight or more). In addition, from the viewpoint of imparting appropriate aggregation to the adhesive, the proportion of the above-mentioned component (C) is usually preferably about 35% by weight or less, more preferably about 30% by weight or less, and further preferably about 25% by weight or less. In one embodiment, the proportion of the above-mentioned component (C) can be set to, for example, about 15 to 30% by weight.

[0130] (Any monomer)

[0131] The monomer components in the art disclosed herein may contain monomers other than the above-mentioned (A) component, (B) component, and (C) component (hereinafter also referred to as “arbitrary monomers”).

[0132] Examples of the above-mentioned optional monomers include (meth)acrylic acid alkyl esters that are not included in the (A) component, that is, (meth)acrylic acid alkyl esters in which the carbon number of the alkyl group is 1 or 19 or more (e.g., 19 to 24). Specific examples of such (meth)acrylic acid alkyl esters include methyl (meth)acrylate, n-nonadecyl (meth)acrylate, iso-nonadecyl (meth)acrylate, n-eicosyl (meth)acrylate, iso-eicosyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0133] Other examples of the above-mentioned optional monomers include monomers containing functional groups other than hydroxyl groups and carboxyl groups. Such functional group-containing monomers can be used for the purpose of introducing crosslinking points into the acrylic polymer or increasing the cohesive force of the acrylic polymer. Examples of the functional group-containing monomer include: amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N-hydroxymethyl(meth)acrylamide; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, and 2-(meth)acrylamide-2-methylpropanesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethylacryloyl phosphate; ketone group-containing monomers such as diacetone(meth)acrylamide, diacetone(meth)acrylate, vinylmethylketone, and vinylacetoacetate; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; alkoxysilyl group-containing monomers such as 3-(meth)acryloyloxypropyltrimethoxysilane and 3-(meth)acryloyloxypropyltriethoxysilane, etc. These monomers may be used alone or in combination of two or more.

[0134] The monomer components in the technology disclosed herein may also contain copolymerizable monomers other than the above-mentioned monomers that can copolymerize with the above-mentioned (A), (B), and (C) components as the above-mentioned arbitrary monomers for the purpose of adjusting the glass transition temperature (Tg) of the acrylic polymer or improving the cohesive force. Examples of such copolymerizable monomers include: carboxylic acid vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrene (α-methylstyrene, etc.), and vinyltoluene; (meth)acrylates containing aromatic rings such as aryl (meth)acrylates (such as phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (such as phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (such as benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and macromonomers having a free radical polymerizable vinyl group at the end of a monomer polymerized with a vinyl group. These can be used individually by 1 type or in combination of 2 or more types.

[0135] The usage amount of these arbitrary monomers is not particularly limited and can be appropriately determined. Usually, it is appropriate that the total usage amount of any monomer is set to be less than about 50% by weight of the monomer component, preferably set to about 30% by weight or less, and more preferably set to about 20% by weight or less. The technology disclosed herein can be preferably implemented in a manner that the total usage amount of any monomer is about 10% by weight or less (for example, about 5% by weight or less) of the monomer component. In the case of using any monomer, from the viewpoint of appropriately exerting the effect of improving adhesion and cohesion, it is appropriate to set the usage amount of the arbitrary monomer to about 0.5% by weight or more of the monomer component, preferably set to about 0.8% by weight or more. In addition, the technology disclosed herein can also be preferably implemented in a manner that does not substantially use any monomer (for example, the usage amount of any monomer is about 0.3% by weight or less of the monomer component, typically about 0.1% by weight or less).

[0136] The above-mentioned (A) component, (B) component, (C) component and arbitrary monomers are typically monofunctional monomers. In addition to such monofunctional monomers, the above-mentioned monomer components may contain a suitable amount of multifunctional monomers as required for the purpose of adjusting the storage elastic modulus of the adhesive layer. Here, in this specification, a monofunctional monomer refers to a monomer having only one polymerizable functional group (typically a free radical polymerizable functional group) containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group. In contrast, a multifunctional monomer, as described below, refers to a monomer having at least two such polymerizable functional groups.

[0137] (Multifunctional monomer)

[0138] The polyfunctional monomer is a monomer having at least two polymerizable functional groups (typically radical polymerizable functional groups) containing an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. Examples of the multifunctional monomer include esters of polyols and (meth)acrylic acid such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; and allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. As suitable examples thereof, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate and dipentaerythritol hexa(meth)acrylate can be cited. Among them, as a preferred example, 1,6-hexanediol diacrylate (HDDA) can be cited. The multifunctional monomer can be used alone or in combination of two or more. From the viewpoint of reactivity, a multifunctional monomer having two or more acryloyl groups is generally preferred.

[0139] The amount of the multifunctional monomer used is not particularly limited, and can be appropriately limited to achieve the purpose of use of the multifunctional monomer. In some embodiments, the amount of the multifunctional monomer used can be set to less than about 3% by weight of the above-mentioned monomer component, preferably less than about 2% by weight, and more preferably less than about 1% by weight (for example, less than about 0.7% by weight). The lower limit of the amount used when using a multifunctional monomer is not particularly limited as long as it is greater than 0% by weight. It is usually appropriate to set the amount of the multifunctional monomer used to more than about 0.001% by weight of the monomer component (for example, more than about 0.01% by weight), and it can be set to more than 0.05% by weight or more than 0.1% by weight.

[0140] Although not particularly limited, the total amount of component (A), component (B) and component (C) in the above-mentioned monomer component as a whole is typically greater than about 50% by weight, preferably about 70% by weight or more, more preferably about 80% by weight or more, and further preferably about 90% by weight or more. The technology disclosed herein can be preferably implemented in a manner where the ratio of the above-mentioned total amount is about 95% by weight or more (e.g., about 99% by weight or more). The ratio of the above-mentioned total amount can also be 100% by weight. The technology disclosed herein can be preferably implemented in a manner where the ratio of the above-mentioned total amount in the above-mentioned monomer component as a whole is 99.999% by weight or less (e.g., 99.99% by weight or less).

[0141] The Tg of the copolymer corresponding to the composition of the above-mentioned monomer components is not particularly limited, and for example, it can be above about -70°C. When the Tg of the copolymer is high, there is a tendency that once optical distortion occurs on the adhesive layer, it is difficult to eliminate it afterwards. Therefore, it is particularly meaningful to apply the technology disclosed herein to suppress the occurrence of optical distortion. On the other hand, a high Tg of the copolymer is beneficial to improving the aggregation of the adhesive layer. In some embodiments, the Tg of the above-mentioned copolymer can be, for example, above about -60°C, preferably above about -55°C, more preferably above about -50°C, or above about -45°C. The technology disclosed herein can also be preferably implemented in a manner where the Tg of the above-mentioned copolymer is above about -40°C (for example, above about -35°C), or further above about -30°C. In addition, it is appropriate that the Tg of the above-mentioned copolymer is generally below about 0°C, and from the viewpoint of the adhesion of the adhesive sheet, low temperature characteristics, etc., it is preferably below about -10°C. In some embodiments, the Tg of the above-mentioned copolymer can be below about -15°C, or below -20°C. The technology disclosed herein can be preferably implemented in an embodiment in which the Tg of the copolymer is, for example, about -30°C or higher and about -10°C or lower.

[0142] Here, the Tg of the copolymer corresponding to the composition of the monomer components refers to the Tg obtained by the Fox equation based on the composition of the above-mentioned monomer components. As shown below, the Fox equation is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0143] 1 / Tg=Σ(Wi / Tgi)

[0144] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K). In this specification, the calculation of Tg is performed only considering monofunctional monomers. Therefore, when the monomer component contains a multifunctional monomer, the total amount of the monofunctional monomers contained in the monomer component is set to 100% by weight, and Tg is calculated based on the Tg of the homopolymer of each monofunctional monomer and the weight fraction of the monofunctional monomer relative to the above total amount.

[0145] As the glass transition temperature of the homopolymer used for calculating Tg, the value described in the known documents is applied. For example, for the monomers listed below, the following values ​​are used as the glass transition temperature of the homopolymer of the monomer.

[0146]

[0147]

[0148] For the glass transition temperature of the homopolymer of monomers other than the monomers exemplified above, the numerical values ​​recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. For monomers for which multiple values ​​are recorded in this document, the highest value is adopted. For monomers for which the glass transition temperature of the homopolymer is not recorded in the above-mentioned Polymer Handbook, the value obtained by the measurement method described in the Japanese Patent Application Publication No. 2007-51271 is used. For monomers for which the nominal value of the glass transition temperature of the homopolymer is provided by a manufacturer, the nominal value may also be adopted.

[0149] <Adhesive composition>

[0150] The adhesive layer in the technology disclosed herein can be formed using an adhesive composition containing the monomer components of the above composition in the form of a polymer, an unpolymer (i.e., a polymerizable functional group is in an unreacted form) or a mixture thereof. The above adhesive composition can be in various forms such as a composition containing an adhesive (adhesive component) in an organic solvent (solvent-type adhesive composition), a composition in which an adhesive is dispersed in an aqueous solvent (water-dispersible adhesive composition), a composition prepared in the form of an adhesive formed by curing with active energy rays such as ultraviolet rays and radiation (active energy ray-curable adhesive composition), and a hot-melt adhesive composition that forms an adhesive when applied in a heated and molten state and cooled to near room temperature.

[0151] Here, in this specification, "active energy rays" refer to energy rays having energy capable of inducing chemical reactions such as polymerization reaction, crosslinking reaction, decomposition of initiators, etc. Examples of active energy rays here include: light such as ultraviolet rays, visible rays, infrared rays; radiation such as α rays, β rays, γ rays, electron beams, neutron rays, X-rays, etc.

[0152] The above-mentioned adhesive composition typically contains at least a part of the monomer components of the composition in the form of a polymer (it can be a part of the type of monomer or a part of the amount). The polymerization method for forming the above-mentioned polymer is not particularly limited, and various polymerization methods known in the art can be appropriately adopted. For example, thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization (typically carried out in the presence of a thermal polymerization initiator); photopolymerization by irradiation with light such as ultraviolet rays (typically carried out in the presence of a photopolymerization initiator); radiation polymerization by irradiation with radiation such as β rays and γ rays, etc. Among them, photopolymerization is preferred. In these polymerization methods, the polymerization method is not particularly limited, and the existing known monomer supply method, polymerization conditions (temperature, time, pressure, light irradiation, radiation irradiation, etc.), materials used other than monomers (polymerization initiators, surfactants, etc.) can be appropriately selected.

[0153] During the polymerization, a known or commonly used photopolymerization initiator or thermal polymerization initiator can be used according to the polymerization method, polymerization form, etc. Such polymerization initiators can be used alone or in combination of two or more.

[0154] The photopolymerization initiator is not particularly limited, and for example, ketal-type photopolymerization initiators, acetophenone-type photopolymerization initiators, benzoin ether-type photopolymerization initiators, acylphosphine oxide-type photopolymerization initiators, α-ketol-type photopolymerization initiators, aromatic sulfonyl chloride-type photopolymerization initiators, photoactive oxime-type photopolymerization initiators, benzoin-type photopolymerization initiators, benzyl-type photopolymerization initiators, benzophenone-type photopolymerization initiators, thioxanthone-type photopolymerization initiators, etc. can be used.

[0155] Specific examples of the ketal-based photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one (for example, trade name “Irgacure 651” manufactured by BASF Corporation).

[0156] Specific examples of acetophenone-based photopolymerization initiators include: 1-hydroxycyclohexyl-phenyl-ketone (for example, the trade name "Irgacure 184" manufactured by BASF), 4-phenoxydichloroacetophenone, 4-tert-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (for example, the trade name "Irgacure 2959" manufactured by BASF), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (for example, the trade name "Darocur 1173" manufactured by BASF), methoxyacetophenone, etc.

[0157] Specific examples of the benzoin ether-based photopolymerization initiator include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether.

[0158] Specific examples of the acylphosphine oxide-based photopolymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (e.g., trade name “Irgacure 819” manufactured by BASF), bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (e.g., trade name “Lucirin TPO” manufactured by BASF), bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the like.

[0159] Specific examples of α-ketol photopolymerization initiators include: 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one, etc. Specific examples of aromatic sulfonyl chloride photopolymerization initiators include: 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime photopolymerization initiators include: 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin photopolymerization initiators include: benzoin, etc. Specific examples of benzyl photopolymerization initiators include: benzyl, etc.

[0160] Specific examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenylketone.

[0161] Specific examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0162] The thermal polymerization initiator is not particularly limited, and for example, an azo polymerization initiator, a peroxide initiator, a redox initiator based on a combination of a peroxide and a reducing agent, a substituted ethane initiator, and the like can be used. More specifically, examples include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate; persulfates such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, tert-butyl hydroperoxide, and hydrogen peroxide; substituted ethane initiators such as phenyl-substituted ethane; redox initiators such as a combination of a persulfate and sodium bisulfite, and a combination of a peroxide and sodium ascorbate, but are not limited thereto. In addition, thermal polymerization can be preferably carried out at a temperature of about 20 to 100° C. (typically 40 to 80° C.), for example.

[0163] The amount of such a thermal polymerization initiator or photopolymerization initiator used may be set to a normal amount used in accordance with the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example, about 0.01 to 1 part by weight) of the polymerization initiator may be used relative to 100 parts by weight of the monomer to be polymerized.

[0164] (Adhesive composition containing polymer of monomer component and unpolymerized substance)

[0165] The adhesive composition of a preferred embodiment contains a polymerized product of a monomer mixture, and the monomer mixture contains at least a portion of the monomer components (raw monomers) of the composition. Typically, a portion of the above-mentioned monomer components is contained in the form of a polymer, and the remainder is contained in the form of an unpolymerized product (unreacted monomer). The adhesive composition comprising a polymer of a monomer component and an unpolymerized product, for example, can be preferably used as an active energy ray-curable adhesive composition. The polymerized product of the above-mentioned monomer mixture can be prepared by polymerizing at least part of the monomer mixture.

[0166] The polymerized product is preferably a partial polymer of the monomer mixture. This partial polymer is a mixture of a polymer derived from the monomer mixture and unreacted monomers, and is typically in a slurry state (a viscous liquid state). Hereinafter, the partial polymer of this property is sometimes referred to as "monomer slurry" or simply "slurry".

[0167] The polymerization method when obtaining the above-mentioned polymerization reaction product is not particularly limited, and the above-mentioned various polymerization methods can be appropriately selected and used. From the viewpoint of efficiency and simplicity, photopolymerization can be preferably adopted. Through photopolymerization, the polymerization conversion of the above-mentioned monomer mixture can be easily controlled by polymerization conditions such as the irradiation amount of light (amount of light).

[0168] The polymerization conversion rate (monomer conversion rate) of the monomer mixture in the above-mentioned partial polymer is not particularly limited. The above-mentioned polymerization conversion rate can be set to, for example, about 70 weight % or less, preferably about 60 weight % or less. From the viewpoints of the ease of preparation, coating properties, etc. of the adhesive composition containing the above-mentioned partial polymer, usually, the above-mentioned polymerization conversion rate is suitable for about 50 weight % or less, preferably about 40 weight % or less (for example, about 35 weight % or less). The lower limit of the polymerization conversion rate is not particularly limited, and is typically about 1 weight % or more, and is usually suitable for about 5 weight % or more.

[0169] The adhesive composition containing the partial polymer of the above-mentioned monomer mixture can be easily obtained by, for example, partially polymerizing the monomer mixture containing all raw monomers by an appropriate polymerization method (e.g., photopolymerization method). Other components (e.g., photopolymerization initiator, multifunctional monomer, crosslinking agent, acrylic acid oligomer described later, etc.) used as needed can be mixed into the adhesive composition containing the above-mentioned partial polymer. The method of mixing such other components is not particularly limited, for example, it can be included in the above-mentioned monomer mixture in advance, or it can be added to the above-mentioned partial polymer.

[0170] In addition, the adhesive composition disclosed herein may also be a form in which a partial polymer of a monomer mixture containing some types of monomers in the monomer component (raw monomer) or a complete polymer is dissolved in the remaining types of monomers or their partial polymers. This form of adhesive composition is also included in the example of an adhesive composition containing a polymer of a monomer component and an unpolymerized polymer. It should be noted that in this specification, "complete polymer" means that the polymerization conversion rate is greater than 95% by weight.

[0171] As a curing method (polymerization method) when forming an adhesive from a polymer containing monomer components and an unpolymerized adhesive composition, photopolymerization can be preferably used. Among adhesive compositions containing polymerized reactants prepared by photopolymerization, it is particularly suitable to use photopolymerization as its curing method. Since the polymerized reactants obtained by photopolymerization already contain photopolymerization initiators, when the adhesive composition containing the polymerized reactants is further cured to form an adhesive, it can be photocured even without adding new photopolymerization initiators. Alternatively, it can also be an adhesive composition of a composition in which a photopolymerization initiator is added as needed to the polymerized reactants prepared by photopolymerization. The additional photopolymerization initiator can be the same as or different from the photopolymerization initiator used in the preparation of the polymerized reactants. An adhesive composition prepared by a method other than photopolymerization can be photocurable by adding a photopolymerization initiator. A photocurable adhesive composition has the advantage that it is easy to form even a thick adhesive layer. In a preferred embodiment, photopolymerization when forming an adhesive from an adhesive composition can be carried out by ultraviolet irradiation. Well-known high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, etc. can be used for ultraviolet irradiation.

[0172] (Adhesive composition containing monomer components in the form of a complete polymer)

[0173] Another preferred embodiment of the adhesive composition contains the monomer components of the adhesive composition in the form of a fully polymerized product. Such an adhesive composition may be in the form of, for example, a solvent-based adhesive composition containing a fully polymerized acrylic polymer as a monomer component in an organic solvent, or a water-dispersible adhesive composition in which the acrylic polymer is dispersed in an aqueous solvent.

[0174] (Crosslinking agent)

[0175] The adhesive composition disclosed herein may contain a crosslinking agent. As the crosslinking agent, a crosslinking agent known or commonly used in the field of adhesives can be used. For example, epoxy crosslinking agents, isocyanate crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, etc. can be listed. These can be used alone or in combination of two or more.

[0176] The content of the crosslinking agent (the total amount when containing two or more crosslinking agents) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as adhesion and cohesion in a well-balanced manner, it is appropriate that the content of the crosslinking agent is generally set to about 5 parts by weight or less relative to 100 parts by weight of the monomer components contained in the adhesive composition, preferably about 0.001 to 5 parts by weight, more preferably about 0.001 to 4 parts by weight, and further preferably about 0.001 to 3 parts by weight. Alternatively, it may be an adhesive composition that does not contain the above-mentioned crosslinking agent.

[0177] (Acrylic oligomer)

[0178] From the viewpoint of improving the bonding strength, etc., an acrylic acid oligomer may be contained in the adhesive composition disclosed herein. As the acrylic acid oligomer, a polymer having a Tg higher than the Tg of the copolymer corresponding to the composition of the above-mentioned monomer components (typically, roughly corresponding to the Tg of the acrylic acid polymer contained in the adhesive formed by the adhesive composition) is preferably used. By containing an acrylic acid oligomer, the bonding strength of the adhesive can be improved.

[0179] For the acrylic oligomer, it is desirable that Tg is about 0°C or more and about 300°C or less, preferably about 20°C or more and about 300°C or less, and more preferably about 40°C or more and about 300°C or less. When Tg is within the above range, the adhesive force can be suitably improved. It should be noted that the Tg of the acrylic oligomer is the same as the Tg of the copolymer corresponding to the composition of the above monomer components, and is a value calculated based on the Fox formula.

[0180] The weight average molecular weight (Mw) of the acrylic acid oligomer can typically be about 1000 or more and about less than 30000, preferably about 1500 or more and about less than 20000, and more preferably about 2000 or more and about less than 10000. By having Mw within the above range, good adhesion and retention characteristics can be obtained, so it is preferred. The Mw of the acrylic acid oligomer can be measured by gel permeation chromatography (GPC) and obtained in the form of a value converted to standard polystyrene. Specifically, TSKgelGMH-H (20) × 2 roots can be used as columns in HPLC8020 manufactured by Tosoh Corporation, and the measurement is carried out in a tetrahydrofuran medium at a flow rate of about 0.5 ml / min.

[0181] Examples of the monomers constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; (meth)acrylates obtainable from terpene compound derivative alcohols, etc. Such (meth)acrylates may be used alone or in combination of two or more.

[0182] As the acrylic oligomer, from the viewpoint of further improving the adhesion of the adhesive layer, it is preferred that the acrylic oligomer contain, as a monomer unit, an acrylic monomer having a relatively bulky structure, represented by (meth)acrylic acid esters having a cyclic structure, such as (meth)acrylic acid esters having a branched alkyl group, such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate, (meth)acrylic acid esters having a branched alkyl group, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate, and (meth)acrylic acid esters having a cyclic structure, such as (meth)acrylic acid esters having a phenyl (meth)acrylate and benzyl (meth)acrylate. In addition, when ultraviolet rays are used during the synthesis of the acrylic oligomer or during the preparation of the adhesive layer, it is preferred that the acrylic oligomer have a saturated bond, and (meth)acrylic acid esters having a branched alkyl group, or esters with alicyclic alcohols can be suitably used as monomers constituting the acrylic oligomer.

[0183] From this viewpoint, suitable acrylic oligomers include, for example, homopolymers such as dicyclopentanyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), dicyclopentanyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA); copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), copolymers of ADA and methyl methacrylate (MMA), copolymers of DCPMA and IBXMA, and copolymers of DCPMA and MMA.

[0184] When the adhesive composition disclosed herein contains an acrylic oligomer, the content thereof is not particularly limited. From the viewpoint of easily realizing an adhesive layer having a preferred storage elastic modulus disclosed herein, the content of the acrylic oligomer is usually preferably set to about 20 parts by weight or less, more preferably about 15 parts by weight or less, and further preferably about 10 parts by weight or less relative to 100 parts by weight of the monomer components contained in the adhesive composition. The technology disclosed herein can also be preferably implemented in a manner not using an acrylic oligomer.

[0185] In addition, the adhesive composition disclosed herein may contain various additives known in the field of adhesives as needed. For example, colorants such as dyes or pigments, antistatic agents, surfactants, plasticizers, tackifying resins, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, inhibitors, inorganic or organic fillers, metal powders, granular materials, foil materials, etc. may be appropriately added according to the application.

[0186] In the technology disclosed herein, as an adhesive composition for forming an adhesive layer, an active energy ray-curable adhesive composition (typically a photocurable adhesive composition) can be preferably used. As the above-mentioned active energy ray-curable adhesive composition, from the viewpoint of environmental hygiene, it is preferably substantially free of organic solvents. For example, it is preferred that the content of the organic solvent is about 5% by weight or less (more preferably about 3% by weight or less, for example, about 0.5% by weight or less). In addition, as described later, from the perspective of forming an adhesive layer by a method suitable for curing the liquid film of the adhesive composition between the A surface of the first film and the second film as described later, a solvent-free adhesive composition is preferred. Here, in this specification, a solvent-free adhesive composition refers to an adhesive composition that does not substantially contain a solvent (for the protection of the meaning of an organic solvent and an aqueous solvent.). For example, it is preferred that the content of the solvent is about 5% by weight or less (more preferably about 3% by weight or less, for example, about 0.5% by weight or less). It should be noted that the solvent refers to a volatile component that should be removed during the formation of the adhesive layer, that is, a volatile component that is not desired to be a constituent component of the finally formed adhesive layer.

[0187] <Laminated sheet>

[0188] The method for manufacturing the laminated sheet disclosed herein is not particularly limited. For example, an adhesive layer can be formed on the A surface of the film of any one of the first film and the second film by applying an adhesive composition and drying or curing it, and another film can be stacked on the surface of the adhesive layer on the opposite side of the A surface, thereby obtaining a laminated sheet. Alternatively, an adhesive layer can be formed by drying or curing the adhesive composition sandwiched between the A surfaces of the first film and the second film, thereby forming a laminated sheet. As the coating method of the adhesive composition, various methods known to the public can be used. Specifically, methods such as roller coating, roller lick coating, gravure coating, reverse roller coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, curtain coating, lip coating, extrusion coating methods such as die coaters, etc. can be listed.

[0189] Laminated sheet disclosed herein can be suitably prepared by being included in the method that the liquid film of adhesive composition is dried or solidified so as to form adhesive layer on the stripping surface of stripping film.When utilizing this method, the adhesive composition (liquid film) with the state of fluidity contacts and dries or solidifies with the above-mentioned stripping surface, thus can accurately control the smoothness of the adhesive layer surface formed by contacting with this stripping surface.As the above-mentioned stripping film, the film that A face is the stripping surface in the first film and the second film can be used.The above-mentioned stripping surface is typically the surface that the maximum peak height (Rp) is less than 50nm.By using the stripping film with the high stripping surface of smoothness like this, the adhesive surface of high smoothness can be manufactured stably (good reproducibility).

[0190] The laminated sheet disclosed herein can be preferably manufactured by a method comprising solidifying a liquid film of the above-mentioned adhesive composition between the A surfaces of the first film and the second film to form an adhesive layer. As a method for configuring a liquid film of an adhesive composition between the A surfaces of the first film and the second film, a method of applying a liquid adhesive composition to the A surface of a film, and then coating another film on the liquid film of the adhesive composition can be adopted. As other methods, a method of supplying the first film and the second film between a pair of rollers in a manner that the A surfaces are opposite to each other and supplying a liquid adhesive composition between their A surfaces can be cited. It should be noted that the coating of the adhesive composition is preferably carried out at below 80°C, more preferably below 60°C (for example, below 40°C). Thus, an adhesive surface with a higher smoothness and a suppressed roughness on the surface of the adhesive layer caused by the difference in the thermal expansion coefficients of the first film, the second film and the adhesive layer can be formed.

[0191] The thickness of the adhesive layer is not particularly limited. The thickness of the adhesive layer can be, for example, about 1 μm to 1000 μm, and it is usually appropriate to set it to about 5 μm to 250 μm. In some embodiments, the thickness of the adhesive layer can be, for example, more than 10 μm, preferably more than 20 μm, more preferably more than 25 μm, and can also be greater than 25 μm. When the thickness of the adhesive layer becomes thicker, there is a tendency for the stress dispersion ability in the adhesive layer to become higher. This is conducive to reducing optical distortion. The technology disclosed herein can be preferably implemented in a manner in which the thickness of the adhesive layer is, for example, more than 30 μm. The thickness of the above-mentioned adhesive layer can be more than 35 μm, or more than 40 μm, or more than 45 μm. On the other hand, when the thickness of the adhesive layer becomes thicker, since the light path passing through the adhesive layer also becomes longer, it is easy to identify optical distortion. Therefore, in some embodiments, it is appropriate to set the thickness of the adhesive layer to, for example, less than 200 μm, or less than 150 μm, or less than 100 μm, or less than 70 μm.

[0192] In the technology disclosed herein, the adhesive sheet (including an adhesive layer and may also include a supporting substrate, but not a release film) constituting the laminated sheet preferably has a haze value of 3% or less. Such an adhesive sheet can be preferably used in various applications including applications requiring transparency. In a roll of a laminated sheet that can be used for optical applications (for example, for the manufacture of optical components), it is particularly meaningful that the haze value of the adhesive sheet is 3% or less. In some embodiments, the haze value of the adhesive sheet is preferably 0 to 2.5%, more preferably 0 to 2%, and may also be, for example, 0 to 1.5%, or 0 to 1%. The above haze value can be measured using a haze meter by attaching the adhesive sheet of the object to be measured to a single surface of an alkaline glass plate. As a haze meter, MR-100 manufactured by Murakami Color Technology Research Institute or its equivalent can be used. During the measurement, the alkaline glass plate to which the adhesive sheet is attached is arranged so that the adhesive sheet becomes the light source side. When the alkaline glass itself has a haze value, the value obtained by subtracting the haze value of the alkaline glass plate itself from the measured value is used as the haze value of the adhesive sheet. As the alkaline glass plate, for example, slide glass S1214 manufactured by Matsunami Glass Industries, Ltd. can be used.

[0193] The haze value of the adhesive layer contained in the laminated sheet disclosed herein is preferably 3% or less. An adhesive sheet having such an adhesive layer (a double-sided adhesive sheet without a substrate including an adhesive layer, or a single-sided adhesive sheet including an adhesive layer and a supporting substrate laminated on the second surface of the adhesive layer) can be preferably used for various purposes including optical purposes. In several embodiments, the haze value of the adhesive layer is preferably 0 to 2.5%, more preferably 0 to 2%, can be 0 to 1.5%, or can be 0 to 1%. The technology disclosed herein can be preferably implemented in a manner where the haze value of the adhesive layer is 0% or more and less than 0.5% (more preferably 0% or more and 0.4% or less, for example 0% or more and 0.3% or less). For the haze value of the adhesive layer, except that the adhesive layer as the object of measurement is attached to a single side of an alkaline glass plate, it can be measured in the same manner as the haze value of the adhesive sheet. It should be noted that in a laminated sheet in which both the first film and the second film are release films, since the adhesive sheet constituting the above-mentioned laminated sheet includes the above-mentioned adhesive layer, the haze value of the adhesive sheet is consistent with the haze value of the adhesive layer.

[0194] The width of the laminate disclosed herein is typically more than 5mm, for example, can be more than 10mm, preferably more than 20mm, more preferably more than 30mm, can be more than 50mm, can be more than 150mm, can be more than 300mm, can also be more than 500mm. When the width of the laminate becomes larger, there is a tendency to easily produce optical distortion caused by the uneven expansion and contraction of the adhesive layer. Therefore, it is particularly meaningful to apply the technology disclosed herein to suppress the optical distortion of the adhesive layer. In addition, from the viewpoints such as handleability, the width of the above-mentioned laminate is usually appropriate for about 5m or less, for example, can be about 4m or less, can be about 3m or less, can be about 2m or less, can also be about 1m or less.

[0195] The total thickness of the laminated sheet disclosed herein is not particularly limited, and may be, for example, about 30 μm to 1500 μm. Here, the total thickness of the laminated sheet refers to the thickness from the B surface of the first film to the B surface of the second film. In some embodiments, the total thickness of the laminated sheet may be, for example, 60 μm or more, 80 μm or more, 105 μm or more, 125 μm or more, or 140 μm or more. In addition, from the viewpoint of the ease of forming a roll, the elongation of the laminated sheet, etc., in some embodiments, the total thickness of the laminated sheet may be, for example, less than 1000 μm, less than 500 μm, or less than 300 μm.

[0196] The laminated sheet disclosed herein preferably has a shear peeling force Fs1 of 0.5 N / 4 cm on the A surface of the first film relative to the first surface of the adhesive layer. 2 Above and 250N / 4cm 2 By setting the shear peeling force Fs1 of the A surface of the first film within the above range, the effect of restricting the free expansion and contraction of the adhesive layer can be well exerted to appropriately suppress the generation of optical distortion. In some embodiments, from the viewpoint of improving the effect of restricting the above expansion and contraction, the shear peeling force Fs1 of the A surface of the first film is preferably 1.0N / 4cm 2 More preferably 5.0N / 4cm 2 Above, can be 10N / 4cm 2 Above, can be 15N / 4cm 2 Above, can be 25N / 4cm 2 Above, can be 35N / 4cm 2 Above, can be 45N / 4cm 2 Above, 55N / 4cm is also possible 2 In addition, from the perspective of peeling operability when peeling the first film from the adhesive layer when using the laminated sheet, in some embodiments, the shear peeling force Fs1 of the A surface of the first film can be, for example, 200N / 4cm 2Below, can be 170N / 4cm 2 Below, can be 150N / 4cm 2 Below, can be 100N / 4cm 2 Below, can be 80N / 4cm 2 Below, 70N / 4cm is also possible 2 the following.

[0197] In the embodiment where the second film is a release film, the shear peeling force Fs2 of the A surface of the second film relative to the second surface of the adhesive layer is preferably 0.5 N / 4 cm from the viewpoint of suppressing the optical distortion of the adhesive layer. 2 Above and 250N / 4cm 2 In some embodiments, for the same reason as for the first film, the shear peeling force Fs2 of the A surface of the second film is preferably 1.0 N / 4 cm 2 More preferably 5.0N / 4cm 2 Above, can be 10N / 4cm 2 Above, can be 15N / 4cm 2 Above, in addition, for example, it can be 200N / 4cm 2 Below, can be 170N / 4cm 2 Below, can be 150N / 4cm 2 Below, can be 100N / 4cm 2 Below, can be 80N / 4cm 2 Below, 70N / 4cm is also possible 2 the following.

[0198] In the case where the second film is a release film, the shear peeling force Fs1 [N / 4cm 2 ] Shear peeling force Fs2 [N / 4cm on the A surface of the second film 2 ] is preferably set to satisfy Fs1<Fs2. Thus, when the first film is to be peeled off from the first side of the adhesive layer, the second side of the adhesive layer can be prevented from floating off from the second film. In this method, the shear peeling force Fs1 of the A side of the first film is usually 170N / 4cm 2 The following is suitable, preferably 150N / 4cm 2 Below, can be 100N / 4cm 2 Below, can be 80N / 4cm 2 Below, 70N / 4cm is also possible 2 From the viewpoint of improving the peeling operability of the first film, in some embodiments, the shear peeling force Fs1 may be 55 N / 4 cm 2 Below, can be 45N / 4cm2 Below, can be 35N / 4cm 2 Below, 25N / 4cm is also possible 2 In the above embodiment, the shear peeling force Fs2 of the A surface of the second film is usually 10N / 4cm 2 The above is appropriate, it can be 15N / 4cm 2 Above, can be 30N / 4cm 2 Above, can be 50N / 4cm 2 Above, 70N / 4cm is also possible 2 above.

[0199] In the case where the second film is a release film, the shear peeling force Fs1 [N / 4cm 2 ] and the shear peeling force Fs2[N / 4cm 2 ] It is preferably set to satisfy the following formula: 30N / 4cm 2 ≤Fs1+Fs2. Thus, the effect of restricting the free expansion and contraction of the adhesive layer can be well exerted to appropriately suppress the generation of optical distortion. In some embodiments, from the viewpoint of improving the effect of restricting the expansion and contraction, the above Fs1+Fs2 is preferably 50N / 4cm 2 More preferably 70N / 4cm 2 Above, can be 90N / 4cm 2 Above, 100N / 4cm is also possible 2 The upper limit of Fs1+Fs2 is not particularly limited, but is usually 400N / 4cm 2 The following is appropriate, which can be 300N / 4cm 2 Below, 250N / 4cm is also possible 2 the following.

[0200] In the case where the second film is a release film, the shear peeling force Fs1 [N / 4cm 2 ] and the shear peeling force Fs2[N / 4cm 2 ] can be set to satisfy the following formula: 0.1≤(Fs2-Fs1) / Fs2. Thus, when the first film is to be peeled off from the first side of the adhesive layer, the phenomenon that the second side of the adhesive layer floats from the second film can be suppressed. From the viewpoint of better suppressing this phenomenon, in some embodiments, (Fs2-Fs1) / Fs2 can be, for example, greater than 0.3, greater than 0.4, or greater than 0.5. In addition, (Fs2-Fs1) / Fs2 is generally appropriate to be less than 1.0, can be less than 0.95, or less than 0.9.

[0201] It should be noted that the shear peeling forces Fs1 and Fs2 can be measured by the method described in the examples described later. The shear peeling forces Fs1 and Fs2 can be adjusted by the selection of the adhesive constituting the adhesive layer (e.g., Tg of the base polymer, monomer composition, etc.), the composition of the A surface of the release film to be measured (e.g., the type of release treatment agent, the thickness of the release treatment layer, etc.), etc.

[0202] <Scroll>

[0203] Matters disclosed in this specification include rolls in the form of any laminated sheet disclosed herein being wound up. Such rolls typically include a core (winding core) and laminated sheets wound around the core. The shape of the core is not particularly limited, and may be, for example, a solid cylindrical shape, a hollow cylindrical shape (i.e., a cylindrical shape), a hollow or solid polygonal prism shape, etc. From the viewpoint of improving the handling properties of the roll, a hollow cylindrical or hollow polygonal prism-shaped core may be preferably used. A cylindrical core is particularly preferred.

[0204] The material constituting the core is not particularly limited, and known materials can be used. Examples thereof include paper such as cardboard; plastic materials such as PE resin, PP resin, vinyl chloride resin, polyester, epoxy resin, phenolic resin, melamine resin, silicone resin, polyurethane, polycarbonate, acrylonitrile-butadiene-styrene copolymer resin (ABS resin); composite materials such as fiber reinforced plastic (FRP); and metal materials such as iron, stainless steel (SUS), and aluminum.

[0205] The outer diameter of the core is not particularly limited. In some embodiments, the outer diameter of the core can be, for example, more than 30 mm, more than 50 mm, more than 70 mm, more than 80 mm, or more than 85 mm. When the outer diameter of the core becomes larger, it is easy to suppress the generation of a grapefruit peel-like surface of the adhesive surface and the tendency of uneven expansion and contraction of the adhesive layer caused by the deformation of the laminated sheet accompanying winding and unwinding. This is preferred from the viewpoint of improving the optical homogeneity of the adhesive layer. On the other hand, for the purpose of improving productivity, etc., it is required to reduce the frequency of changing the roll by lengthening the laminated sheet contained in the roll. In order to lengthen the laminated sheet contained in the roll, it is advantageous for the outer diameter of the core to be small. From this viewpoint, the outer diameter of the core is preferably set to, for example, less than 300 mm, less than 250 mm, less than 200 mm, or less than 180 mm. The technology disclosed herein can also be preferably implemented in the form of a roll body with an outer diameter of the core of 150 mm or less, 100 mm or less, or even 95 mm or less, which can also achieve a laminated sheet with good optical homogeneity of the adhesive layer. It should be noted that in the case of a roll core with a non-circular cross-sectional shape, the diameter of the core refers to the diameter obtained by approximating its cross-sectional shape with a circle.

[0206] In the case of a hollow core, the wall thickness of the core (i.e., the thickness of the outer wall) is not particularly limited, and can be appropriately set to obtain the desired strength in consideration of the material, outer diameter, etc. of the core. From the viewpoint of lightweighting of the roll, the wall thickness of the core is usually about 2 mm to 15 mm, preferably about 3 mm to 10 mm.

[0207] <Application>

[0208] The laminate disclosed herein can achieve excellent optical homogeneity by suppressing the generation of a grapefruit peel-like surface on the adhesive surface and the generation of optical distortion of the adhesive layer. Utilizing this advantage, the laminate can be preferably used for optical purposes, for example. More specifically, the laminate can be suitably used for the manufacture of an optical component (adhesive optical component) having an adhesive layer, for example, in a manner in which the adhesive sheet contained in the laminate is attached to the optical component. In addition, the laminate can preferably be used as an adhesive optical component by directly or processing the adhesive sheet contained in the laminate into an appropriate size and shape in a manner in which the second film has a non-peelable A-side supporting substrate, and the supporting substrate is an optical component.

[0209] When an optical film is used as the above-mentioned optical component, the above-mentioned adhesive optical component can be used as an adhesive optical film. As the above-mentioned optical film, a polarizing plate, a phase difference plate, an optical compensation film, a brightening film, a hard coating (HC) film, an anti-reflection film, an impact absorbing film, an antifouling film, a photochromic film, a dimming film, a wavelength selective absorption film, a wavelength conversion film, and components formed by stacking them can be used. The adhesive layer or adhesive sheet contained in the laminated sheet disclosed herein is also suitable for use in the field of ophthalmology. The above-mentioned adhesive layer or adhesive sheet is not limited to the above-mentioned optical use and ophthalmic use, and can be used in various uses in the form of an adhesive sheet using, for example, a conventional antifouling film, a heat insulation film, an impact absorbing film, etc. as a support.

[0210] The matters disclosed in this specification include the following.

[0211] (1) A laminated sheet comprising: an adhesive layer, a first film laminated on a first surface of the adhesive layer, and a second film laminated on a second surface of the adhesive layer.

[0212] The first film is a release film whose surface A, which is in contact with the adhesive layer, serves as a release surface.

[0213] The maximum peak height Rp of the A surface of the first film 1A Less than 50nm,

[0214] The total thickness T of the first film and the second film SUM It is 80μm or more.

[0215] (2) The laminated sheet according to (1) above, wherein the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer formed from an active energy ray-curable pressure-sensitive adhesive composition (eg, a photocurable pressure-sensitive adhesive composition).

[0216] (3) The laminated sheet according to (1) or (2), wherein the relationship between the thickness T [mm] of at least one (preferably both) of the first film and the second film and the elastic modulus E' [MPa] satisfies the following formula: 0.10 [N·mm] < E' × T 3 .

[0217] (4) The laminate sheet according to any one of (1) to (3) above, wherein the first film and the second film are each independently selected from the group consisting of a polyester resin film, a cellulose resin film, a polyimide resin film, and a polyethersulfone resin film.

[0218] (5) A laminate sheet according to any one of (1) to (4) above, wherein the thickness of at least one of the first film and the second film (preferably both) is 25 μm or more (preferably 35 μm or more, more preferably 50 μm or more, and further preferably 70 μm or more).

[0219] (6) The laminated sheet according to any one of (1) to (5) above, wherein the residual adhesion rate of the A surface of the first film is 60% or more.

[0220] (7) The laminated sheet according to any one of (1) to (6), wherein the shear peeling force Fs1 of the A surface of the first film relative to the first surface of the adhesive layer is 0.5 N / 4 cm 2 Above and 250N / 4cm 2 the following.

[0221] (8) The laminated sheet according to any one of (1) to (7), wherein the maximum peak height Rp of the surface A of the second film in contact with the adhesive layer is 2A Less than 50nm.

[0222] (9) The laminate sheet according to any one of (1) to (8) above, wherein the second film is a release film whose A surface serves as a release surface.

[0223] (10) The laminated sheet according to (9) above, wherein the residual adhesion rate of the A surface of the second film is 60% or more.

[0224] (11) The laminated sheet according to (9) or (10), wherein the shear peeling force Fs2 of the A surface of the second film relative to the second surface of the adhesive layer is 0.5 N / 4 cm 2 Above and 250N / 4cm 2 the following.

[0225] (12) The laminated sheet according to any one of (9) to (11), wherein the shear peeling force Fs1 [N / 4cm] of the A surface of the first film relative to the first surface of the adhesive layer is 2 ] and the shear peeling force Fs2 [N / 4cm] of the A surface of the second film relative to the second surface of the adhesive layer 2 ] satisfies the following formula: 0.1≤(Fs2-Fs1) / Fs2.

[0226] (13) A laminated sheet according to any one of (1) to (12) above, wherein the maximum peak height Rp of the A surface of at least one of the first film and the second film is greater than 20 nm and less than 50 nm, greater than 20 nm and less than 40 nm, or greater than 20 nm and less than 30 nm, and the A surface is a release-treated surface treated with a silicone-based release agent.

[0227] (14) A laminated sheet according to any one of (1) to (13) above, wherein the maximum peak height Rp of the A surface of at least one of the first film and the second film is greater than 20 nm and less than 50 nm, greater than 20 nm and less than 40 nm, or greater than 20 nm and less than 30 nm, and the A surface is a release-treated surface treated with a long-chain alkyl-based release agent.

[0228] (15) A laminated sheet according to any one of (1) to (13) above, wherein the maximum peak height Rp of the A surface of at least one of the first film and the second film is greater than or equal to 5 nm and less than 50 nm, greater than or equal to 5 nm and less than 30 nm, greater than or equal to 5 nm and less than 25 nm, greater than or equal to 10 nm and less than 25 nm, greater than or equal to 15 nm and less than 30 nm, or greater than or equal to 15 nm and less than 25 nm, and the A surface is a release-treated surface treated with a long-chain alkyl-based release treatment agent.

[0229] (16) A laminated sheet according to any one of (1) to (15) above, wherein the A surface of at least one of the first film and the second film is a release-treated surface treated with a silicone-based release agent, and the residual adhesion rate of the release-treated surface is greater than 60%.

[0230] (17) The laminate sheet according to any one of (1) to (16) above, wherein the adhesive layer has a single-layer structure without a substrate.

[0231] (18) The laminated sheet according to any one of (1) to (17) above, wherein the haze value of the pressure-sensitive adhesive sheet after the release film is removed from the laminated sheet is 3% or less.

[0232] (19) The laminate sheet according to any one of (1) to (18) above, wherein the adhesive constituting the adhesive layer is an acrylic adhesive.

[0233] (20) The laminate sheet according to any one of (1) to (19) above, which is used for production of an optical member having the pressure-sensitive adhesive layer.

[0234] (21) The laminated sheet according to any one of (1) to (20) above, which is wound into a roll form.

[0235] Example

[0236] Hereinafter, several embodiments of the present invention will be described, but the present invention is not limited to the scope shown in the specific examples. It should be noted that "parts" and "%" in the following description are based on weight unless otherwise specified.

[0237] <Preparation of Adhesive Composition>

[0238] (Adhesive composition C1)

[0239] 39 parts of n-butyl acrylate, 40 parts of cyclohexyl acrylate, 21 parts of 4-hydroxybutyl acrylate, 0.05 parts of 2,2-dimethoxy-1,2-diphenylethane-1-one (manufactured by IGM Regins, trade name "Omnirad 651") as a photopolymerization initiator, and 0.05 parts of 1-hydroxycyclohexyl-phenyl-ketone (manufactured by IGM Regins, trade name "Omnirad 184") were mixed, and irradiated with ultraviolet rays in a nitrogen atmosphere to prepare a partial polymer (monomer syrup). 0.5 parts of 1,6-hexanediol diacrylate was added to the obtained monomer syrup, and the mixture was uniformly mixed to prepare an adhesive composition C1.

[0240] (Adhesive composition C2)

[0241] 70 parts of 2-ethylhexyl acrylate, 10 parts of N-vinyl pyrrolidone, 20 parts of 4-hydroxybutyl acrylate, 0.05 parts of 2,2-dimethoxy-1,2-diphenylethane-1-one (manufactured by IGM Regins, trade name "Omnirad 651") as a photopolymerization initiator, and 0.05 parts of 1-hydroxycyclohexyl-phenyl-ketone (manufactured by IGM Regins, trade name "Omnirad 184") were mixed, and irradiated with ultraviolet rays under a nitrogen atmosphere to prepare a partial polymer (monomer syrup). 0.2 parts of 1,6-hexanediol diacrylate was added to the obtained monomer syrup, and the mixture was uniformly mixed to prepare an adhesive composition C2.

[0242] <Production of laminated sheets>

[0243] (Example 1)

[0244] As the first film, the surface A to be laminated on the first surface of the adhesive layer is a release surface treated with the silicone-based release agent S1, and the maximum peak height Rp of the surface A is A1 The elastic modulus E' [MPa] and thickness T (0.075 mm) of the PET film were calculated as E' × T (0.075 mm). 3 It is 0.99N·mm.

[0245] In addition, as the second film, the surface A to be laminated on the second surface of the adhesive layer is prepared as a release surface treated with the silicone-based release agent S3, and the maximum peak height Rp of the above-mentioned surface A is A2 The E'×T of the PET film is 23 nm and the thickness is 75 μm. 3 It is 0.99N·mm.

[0246] Adhesive composition C1 is applied to the A surface (peel-off surface) of the above-mentioned first film to form a liquid film of adhesive composition C1 on the A surface. The coating amount of the adhesive composition is adjusted so that the thickness of the adhesive layer finally formed is 50 μm. Next, the second film is coated on the above-mentioned liquid film so that the A surface (peel-off surface) of the second film is in contact with the above-mentioned liquid film. Thus, the above-mentioned liquid film is isolated from oxygen. In this way, in a state where the two sides of the liquid film of the adhesive composition are in contact with the A surfaces of the first film and the second film respectively, a chemical lamp (manufactured by Toshiba Corporation) is used to irradiate for 360 seconds with an illumination of 5 mW / cm 2 The liquid film is cured to form an adhesive layer by a polymerization reaction with ultraviolet rays, thereby obtaining a laminated sheet having a three-layer structure consisting of an adhesive layer (i.e., an ultraviolet cured product of the liquid film), a first film laminated on a first surface of the adhesive layer, and a second film laminated on a second surface of the adhesive layer.

[0247] The above-mentioned illuminance values ​​are measured based on an industrial UV detector (manufactured by TOPCON, trade name “UVR-T1”, light receiving unit model UD-T36) having a peak sensitivity wavelength of about 350 nm.

[0248] (Example 2)

[0249] A laminated sheet was obtained in the same manner as in Example 1 except that the adhesive composition C2 was used instead of the adhesive composition C1.

[0250] (Example 3)

[0251] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was a release surface treated with a long-chain alkyl release agent A1 (the surface of a release treatment layer formed with the release agent A1 and having a thickness of about 300 nm). A1 In addition, as the second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release surface treated with a long-chain alkyl release agent A1 (the surface of a release treatment layer formed using the release agent A1 and having a thickness of about 100 nm). A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0252] (Example 4)

[0253] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was treated with the silicone-based release agent S2. A1 In addition, as the second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release side treated with a silicone-based release agent S3. A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0254] (Example 5)

[0255] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was treated with the silicone-based release agent S2. A1 In addition, as the second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release side treated with a silicone-based release agent S3. A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0256] (Example 6)

[0257] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was treated with the silicone-based release agent S1. A1 In addition, as the second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release side treated with a silicone-based release agent S2. A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0258] (Example 7)

[0259] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was treated with the silicone-based release agent S2. A1 In addition, as the second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release side treated with a silicone-based release agent S3. A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0260] (Example 8)

[0261] As the first film, a film having a thickness and Rp shown in Table 1 was prepared in which the A side was treated with the silicone-based release agent S1. A1 In addition, as a second film, a PET film having a thickness and Rp shown in Table 1 was prepared, wherein the A side was a release side treated with a silicone-based release agent S2. A2 A laminated sheet was obtained in the same manner as in Example 1 except that the first and second films were used.

[0262] It should be noted that as the above-mentioned silicone-based release treatment agent S1, a treatment agent is used, which is prepared by diluting 100 parts of a silicone-based release treatment agent (manufactured by Shin-Etsu Chemical Co., Ltd., KS-847H) and 3.3 parts of a silicone curing catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., CAT-PL-50T) to 0.3% using a mixed solvent containing toluene (manufactured by Idemitsu Petrochemical), n-hexane (manufactured by Maruzen Petrochemical) and methyl ethyl ketone (manufactured by Idemitsu Kosan) in a weight ratio of 1:2:1.

[0263] As the above-mentioned silicone-based release treatment agent S2, a treatment agent prepared by mixing 92 parts of a vinyl-containing silicone-based release treatment agent (manufactured by Shin-Etsu Chemical Co., Ltd., KS-3703), 8 parts of a release control agent (manufactured by Shin-Etsu Chemical Co., Ltd., KS-3800) and 3 parts of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., CAT-PL-50T) with 680 parts of toluene and 680 parts of n-hexane as dilution solvents is used.

[0264] As the above-mentioned silicone-based release treatment agent S3, a treatment agent prepared by mixing 80 parts of a vinyl-containing silicone-based release treatment agent (manufactured by Shin-Etsu Chemical Co., Ltd., KS-3703), 20 parts of a release control agent (manufactured by Shin-Etsu Chemical Co., Ltd., KS-3800) and 3 parts of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., CAT-PL-50T) with 680 parts of toluene and 680 parts of n-hexane as dilution solvents is used.

[0265] As the long-chain alkyl-based release treatment agent A1, an agent obtained as follows was used: 200 parts of p-xylene (Xylol, manufactured by Taiyo Chemical Industry) and 600 parts of octadecyl isocyanate (R-NCO, manufactured by OHARA PARAGIUM CHEMICAL CO., LTD.) were heated while stirring, and after the xylene began to reflux, 100 parts of polyvinyl alcohol (Kuraray Poval 205, manufactured by Kuraray) were added in small amounts over 2 hours at intervals of 10 minutes, and after the addition was completed, the mixture was refluxed for another 2 hours. Then, the reaction mixture was added to methanol to precipitate the reaction product as a white precipitate, and the precipitate was separated by filtration. 140 parts of xylene was added, heated to completely dissolve it, and then methanol was added again to precipitate it. After repeating this operation several times, the precipitate was washed with methanol, dried and pulverized, and the obtained powder was diluted with water to 0.3%, thereby obtaining a product.

[0266] As the first and second films in Examples 1, 2, 4 to 8, films obtained as follows were used: the above-mentioned release agent was applied to one side (the side to be treated) of a PET film as a backing substrate using a bar coater so that the thickness after drying was 80 nm to 150 nm (e.g., about 120 nm), dried at 120° C. for 1 minute, and then aged at 50° C. for 24 hours. It should be noted that the coating amount of the release agent was appropriately adjusted so as to obtain the desired releasability.

[0267] As the first and second films of Example 3, films obtained as follows are used: the above-mentioned release treatment agent is applied on one side (the surface to be treated) of a PET film serving as a backing substrate using a rod coater so that the thickness of the first film after drying is about 300 nm and the thickness of the second film after drying is about 100 nm. After drying at 120°C for 1 minute, the films are aged at 50°C for 24 hours to obtain the films.

[0268] In addition, the maximum peak height Rp of the A surface of the first and second films used in the above examples is A1 , Rp A2The measurement was performed using a stylus surface roughness tester "SV3100S4" manufactured by Mitutoyo Corporation in accordance with JIS B 0601: 2001. As the cutoff value (reference length), 0.08 mm was used when it was estimated to be Ra≤0.02 μm, 0.25 mm was used when it was estimated to be 0.02 μm<Ra≤0.1 μm, and 0.8 mm was used when it was estimated to be 0.1 μm<Ra≤2 μm, based on the arithmetic mean height Ra estimated for the measurement target surface.

[0269] It should be noted that the arithmetic mean height Ra estimated for the measurement target surface can be estimated by measuring the arithmetic mean height Ra of the measurement target surface using a non-contact surface roughness measuring device. As a non-contact surface roughness measuring device, a surface roughness measuring device using a light interference method (e.g., Wyko NT-9100 manufactured by Veeco or its equivalent) can be used. As the arithmetic mean height Ra estimated for the A surface of the first and second films used in the above examples, the value obtained by the following measurement conditions using Wyko NT-9100 manufactured by Veeco is used.

[0270] ·Measurement area / time: 622μm×467μm

[0271] (Objective lens: 10x, FOV (internal lens): 1.0x)

[0272] Measurement mode: VSI (Vertical Scan Interferometry)

[0273] Retrace: 5μm

[0274] ·Measurement distance: 10μm

[0275] Threshold: 0.1%

[0276] Scanning speed: 1x (Single scan)

[0277] <Measurement of shear peel strength>

[0278] The obtained laminated sheet was cut into a size of 20 mm in width and 200 mm in length, the peeling film in contact with the adhesive surface of the object to be measured on the opposite side of the peeling film was peeled off, and a PET film with a thickness of 50 μm was pasted on the exposed adhesive surface as a backing material, and the obtained material was used as a sample for shear peeling force measurement. At a position of 90 mm from one end of the length direction of the above-mentioned sample, the above-mentioned sample was half-cut from the above-mentioned backing material side in a manner of cutting off the above-mentioned backing material and adhesive layer, and the backing material and adhesive layer from one end of the above-mentioned length direction to a range of 90 mm were peeled off from the peeling film of the object to be measured. Next, at a position of 110 mm from one end of the length direction of the above-mentioned sample, the above-mentioned sample was half-cut from the above-mentioned peeling film side of the above-mentioned object to be measured in a manner of only cutting off the peeling film of the object to be measured. Then, a tensile test was conducted using a tensile testing machine (manufactured by Shimadzu Corporation, device name "Tensilon") at a peeling angle of 0 degrees and a tensile speed of 10 mm / min, and the maximum value of the peeling force observed until the peeling film (cut at a position 110 mm from one end in the longitudinal direction) to be measured was peeled off from the adhesive layer was taken as the shear peeling force [N / 4 cm 2 ]. It should be noted that, in the case where the second film is a supporting substrate, the supporting substrate can be used as the above-mentioned backing material to measure the shear peeling force of the first film from the adhesive surface. In addition, in the case where the first and second films are both release films, when the shear peeling force of the release film in contact with the adhesive surface on the opposite side of the release film to be measured is significantly higher than the shear peeling force of the release film to be measured, the operation of sticking the above-mentioned backing material can also be omitted.

[0279] <Making the scroll>

[0280] The laminated sheets of the above examples were prepared as follows: a long film with a width of 1000 mm was used as the first film and the second film, and the adhesive composition was applied to the central portion of the width of the first film with a width of about 930 mm. The two ends of the width of the laminated sheet of each example were cut along the inner side of the width of the adhesive layer formed by the adhesive composition, thereby preparing a roll system working sample with a width of 300 mm and a length of about 30 m.

[0281] A cylindrical core having an outer diameter of 90.2 mm, an inner diameter of 76.2 mm, and an axial length of 305 mm was prepared. One end of the sample in the longitudinal direction (winding start end) was fixed to the outer peripheral surface of the core using a commercially available adhesive tape so that the second film side of each roll-forming sample became the inner peripheral side, and the remaining part of the sample was wound around the core at a winding tension of about 200 N / m to prepare a roll. The other end of the sample in the longitudinal direction (winding end end) was fixed to the outer side surface of the sample located on the inner periphery (surface B of the first film) using a commercially available adhesive tape.

[0282] <Optical distortion>

[0283] After the roll prepared above was stored in a room at 30° C. for 28 days, a roll sample located about 10 m from the winding start end was cut into a size of 300 mm×1000 mm to prepare a sample for optical distortion evaluation.

[0284] The sample (a laminated sheet having a structure of a first film / adhesive layer / second film) was kept in a flat shape, and arranged between a point light source and a screen, with the second film side of the sample as the point light source side, at an angle of about 45 degrees relative to the light beam from the point light source. As the point light source, a xenon lamp C2577 manufactured by Hamamatsu Photonics was used. The distance from the point light source to the screen was set to about 100 cm, and the sample was arranged at a position about half of the distance.

[0285] The point light source was turned on, and the image projected on the screen through the sample was visually observed, and the presence or absence of optical distortion and its degree were evaluated according to the following three levels. The results are shown in Table 1. It should be noted that the evaluation of optical distortion was performed in an environment of 23°C and 50% RH about 5 minutes after the sample for optical distortion evaluation was cut from the roll after storage.

[0286] E: No optical distortion was observed.

[0287] G: Although some optical distortion is observed, it is within the acceptable range for practical use.

[0288] P: Significant optical distortion was observed.

[0289] <Surface smoothness>

[0290] In the evaluation of the optical distortion, the first film was peeled off from the sample to expose the adhesive surface, the exposed adhesive surface and the image projected on the screen were visually observed, and the smoothness of the surface of the adhesive layer (first adhesive surface) was evaluated according to the following three levels.

[0291] E: No grapefruit peel-like surface was observed, and the surface was smooth (excellent surface smoothness).

[0292] G: Generation of a grapefruit peel-like surface was slightly observed, but the degree is tolerable in practical use.

[0293] P: Generation of a grapefruit peel-like surface (lack of surface smoothness) was observed.

[0294] [Table 1]

[0295] Table 1

[0296]

[0297] As shown in Table 1, Rp 1A Less than 50nm, and the total thickness of the first and second films T SUM The laminated sheets of Examples 1 to 5 having a surface smoothness of 80 μm or more and a small optical distortion have good optical homogeneity. 1A In Examples 1 to 3 where Rp is 30 nm or less, particularly high surface smoothness is obtained. 1A In the large cases 6 and 8, sufficient surface smoothness cannot be obtained. SUM In Examples 6 and 7 where the sample size is less than 80 μm, regardless of Rp 1A Regardless of the value of , optical distortion is observed.

[0298] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the scope of protection of the claims. The aspects described in the claims include aspects obtained by variously modifying and changing the specific examples described above.

Claims

1. A laminated sheet comprising: an adhesive layer, a first film laminated on a first surface of the adhesive layer, and a second film laminated on a second surface of the adhesive layer, The first film and the second film are release films whose surfaces in contact with the adhesive layer, namely, surface A, serve as release surfaces. The maximum peak height Rp of the A surface of the first film 1A Less than 50nm, The total thickness T of the first film and the second film SUM 80μm or more, The first film and the second film are polyester resin films respectively. The thickness of the adhesive layer is 20 μm or more and 1000 μm or less, The maximum peak height Rp of the surface A of the second film in contact with the adhesive layer 2A Less than 50nm.

2. The laminate according to claim 1, wherein: The adhesive layer is an adhesive layer formed of an active energy ray-curable adhesive composition.

3. The laminated sheet according to claim 1 or 2, wherein: The relationship between the thickness T [mm] and the elastic modulus E' [MPa] of at least one of the first film and the second film satisfies the following formula: 0.10 [N·mm] < E'×T 3 .

4. The laminated sheet according to claim 1 or 2, wherein: At least one of the first thin film and the second thin film has a thickness of 25 μm or more.

5. The laminated sheet according to claim 1 or 2, wherein: The residual adhesion rate of the A surface of the first film is 60% or more.

6. The laminated sheet according to claim 1 or 2, wherein: The shear peeling force Fs1 of the A surface of the first film with respect to the first surface of the adhesive layer is 0.5 N / 4 cm 2 Above and 250N / 4cm 2 the following.

7. The laminated sheet according to claim 1 or 2, wherein: The maximum peak height Rp of the surface A of the second film in contact with the adhesive layer 2A Below 35nm.

8. The laminated sheet according to claim 1 or 2, wherein: The residual adhesion rate of the A surface of the second film is 60% or more.

9. The laminated sheet according to claim 1 or 2, wherein: The shear peeling force Fs2 of the A surface of the second film relative to the second surface of the adhesive layer is 0.5 N / 4 cm 2 Above and 250N / 4cm 2 the following.

10. The laminated sheet according to claim 1 or 2, wherein: The shear peeling force Fs1 [N / 4cm] of the A surface of the first film relative to the first surface of the adhesive layer 2 ] and the shear peeling force Fs2 [N / 4cm] of the A surface of the second film relative to the second surface of the adhesive layer 2 ] satisfies the following formula: 0.1≤(Fs2-Fs1) / Fs2.

11. The laminated sheet according to claim 1 or 2, wherein: The maximum peak height Rp of the A surface of at least one of the first film and the second film is 20 nm or more and less than 50 nm, and the A surface is a release-treated surface treated with a silicone-based release agent.

12. The laminated sheet according to claim 1 or 2, wherein: The maximum peak height Rp of the A surface of at least one of the first film and the second film is 20 nm or more and less than 50 nm, and the A surface is a release-treated surface treated with a long-chain alkyl-based release agent.

13. The laminated sheet according to claim 1 or 2, wherein: The maximum peak height Rp of the A surface of at least one of the first film and the second film is 5 nm or more and less than 50 nm, and the A surface is a release-treated surface treated with a long-chain alkyl-based release-treating agent.

14. The laminated sheet according to claim 1 or 2, wherein: The A surface of at least one of the first film and the second film is a release-treated surface treated with a silicone-based release agent, and a residual adhesive rate of the release-treated surface is 60% or more.

15. The laminated sheet according to claim 1 or 2, wherein: The adhesive layer is a single-layer structure without a substrate.

16. The laminated sheet according to claim 1 or 2, wherein: The haze value of the pressure-sensitive adhesive sheet after removing the release film from the laminated sheet is 3% or less.

17. The laminated sheet according to claim 1 or 2, wherein: The adhesive constituting the adhesive layer is an acrylic adhesive. 18 . The laminated sheet according to claim 1 or 2, which is used for production of an optical member having the pressure-sensitive adhesive layer.

19. The laminated sheet according to claim 1 or 2, which is wound into a roll form.

Citation Information

Patent Citations

  • Portable electronic equipment

    JP1988000788A

  • Pressure-sensitive adhesive sheet with release film

    CN109627995A

  • Double-sided pressure-sensitive adhesive sheet and method for fixing plastic film

    US20090229733A1